How does the number of chews and temperature impact the sensory properties of plant-based cheese? - Zach Adams; Brianna Power; Matthew B. McSweeney (Food Quality and Preference, 2026)

What is expected of seaweed containing products? Consumer expectations and experiences with seaweed-containing food - Brianna Power; Cayla E.J. Weiler; Zach Adams; Mackenzie Gorman; Matthew B. McSweeney (Food and Humanity, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Informed use of Aliivibrio fischeri Bioluminescence Inhibition Testing for High Strength Aqueous Matrices Treated with Advanced Oxidation Processes - Adam C. Burdsall; Rebecca B. Kriss; Andrea Burkes; Matthew L. Magnuson (Environmental Processes, 2026)

The potential role of wastewater surveillance signals for overdose prevention in Marin County, California, February 2023–June 2024 - Haylea Hannah; Sophie Zhu; Zerleen Quader; Souci Louis; Priyanka Thatipamala; Lee Ann Prebil; Megan Bias; Carly Adams; Heather E Reese; Jessica Ricaldi; Scott Santibañez; Jonathan Yoder; et al. (Water Research, 2026)

Double-stranded RNA and reverse transcriptase signatures of endogenous retroviruses after exposure to spaceflight environment related stressors - Michelle Mendiola Pla; Franklin H. Lee; Matthew F. Smith; Alejandro Alvarez Lobo; Thomas E. Diaz; Adam S. Cockrell; Dawn E. Bowles (Life Sciences in Space Research, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Nostalgia and consumer acceptance of hummus formulated with different seaweed varieties - Matthew Code; Zach Adams; Rachael Moss; Mackenzie Gorman; Matthew B. McSweeney (Algal Research, 2026)

Unequal air pollution removal benefits from city-owned street trees across socioeconomically marginalized neighbourhoods - Siliang Cui; Matthew Adams (Atmospheric Pollution Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Non-negligible disparities in source-specific ambient PM2.5 across economic groups over space and time in China - Yanchuan Shao; Zongwei Ma; Jianxun Yang; Miaomiao Liu; Wen Fang; Matthew Adams; Jun Bi (Journal of Hazardous Materials, 2026)

Integrated machine learning segmentation and 3D change detection for a scalable coastal cliff monitoring workflow - Connor J. Mack; Matthew Maclay; Raphael Krier-Mariani; Adam P. Young (Computers & Geosciences, 2026)

Exploring the impact of tree presence and configuration on ambient NO₂ and O₃ concentrations in urban parks: a case study in Montreal - Lingshan Li; Angela Kross; Samuel Evan Gonzalez-Fleurant; Niraj Dayanandan; Ursula Eicker; Matthew Adams; Carly D. Ziter (Urban Ecosystems, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Impact of different roasting times and temperatures on the sensory properties of luffa (Luffa cylindrica L.) seed powder - Zach Adams; Matthew B. McSweeney (Food and Humanity, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Phylogenomics of poachers (Agonidae) and the evolution of armor in cottoid fishes (Perciformes: Cottoidei) - Megan L. Vandenberg; Zach Heiple; Matthew A. Kolmann; Thaddaeus Buser; Adam P. Summers; Fernando Meléndez-Vazquez; Dahiana Arcila; Katherine P. Maslenikov; Luke Tornabene (Molecular Phylogenetics and Evolution, 2026)

A projection method for particle resampling - Mark F. Adams; Daniel S. Finn; Matthew G. Knepley; Joseph V. Pusztay (Computer Physics Communications, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

High-resolution surface and rootzone soil moisture over US cropland: A novel framework assimilating multi-source remote sensing data, machine learning, and the Layered Green and Ampt Infiltration with Redistribution model - Shuohao Cai; Yijia Xu; Zhengwei Yang; Wade T. Crow; Zhou Zhang; Jiali Shang; Jiangui Liu; Peter La Follette; Chris Reberg-Horton; Harry Schomberg; Steven Mirsky; Brian Davis; et al. (Remote Sensing of Environment, 2026)

Urban air pollution and in vitro fertilization outcomes: A Canadian retrospective study - Vasilia Vastis; Riki Dayan; Michael Neal; Stacy Deniz; Shilpa Amin; Megan Karnis; Karen Kteily; Catherine Friedman; Alison Holloway; Kerstyn Lutz; João Réquia Júnior Weeberb; Matthew Adams; et al. (Reproductive Toxicology, 2026)

Does health information influence consumer perception of seaweed-containing foods? A repeated exposure study - Rachael Moss; Matthew Code; Brianna Power; Zach Adams; Mackenzie Gorman; Matthew B. McSweeney (Algal Research, 2026)

Algal biogenic synthesis of SiO2–CaO–P2O5 system bioactive glass using Cyclotella meneghiniana and waste fish bone - Enobong R. Essien; Victor A. Ajisafe; David A. Faluyi; Ngozi A. Adeleye; Violette N. Atasie; Taofikat Abosede Adesalu; Luqman A. Adams; Matthew Julius (Algal Research, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Development of a River Dynamical Core for E3SM to simulate compound flooding on Exascale-class heterogeneous supercomputers - Gautam Bisht; Donghui Xu; Jeffrey Johnson; Jed Brown; Matthew Knepley; Mark Adams; Dongyu Feng; Dalei Hao; Darren Engwirda; Mukesh Kumar; Zeli Tan (Environmental Modelling & Software, 2026)

Variability of airborne microbial communities and associations with organic pollutants in African air particulate matter across land-use types - Egide Kalisa; Donnabella Lacap-Bugler; Matthew Adams; Jiaqi Bi; Antoine Nsabimana; Gabriel Habiyaremye; Glorieuse Uwizeye; Timothy Lawrence; Kevin Lee; Kazuichi Hayakawa; Stephen Pointing; Stephen DJ. Archer (Atmospheric Environment, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Inflammation and insulin profiles in men assigned to exercise vs. usual care for prostate cancer: results from the active surveillance exercise (ASX) randomized controlled trial - William A. Pace; Adam Olshen; Ye Wang; Stacey A. Kenfield; Erin L. Van Blarigan; Rebecca E. Graff; Janet Cowan; Lufan Wang; Imelda Tenggara; Karen Lopez; Katriel Encabo; Lee W. Jones; et al. (Cancer Causes & Control, 2026)
Objectives Physical activity is associated with reduced risk of prostate cancer (PCa) progression and death; changes in insulin sensitivity and inflammation are potential mediating mechanisms. This study examined whether exercise after PCa diagnosis affects insulin-related and inflammatory biomarkers. Methods The Active Surveillance Exercise (ASX) randomized controlled trial was assigned to men undergoing active surveillance for low-risk, localized PCa to a 16-week exercise intervention (home-based walking program; n = 26) or printed physical activity recommendations (control group; n = 25). Fasting blood samples were collected at baseline and after 16 weeks. Samples were analyzed for markers of insulinemia (insulin, C-peptide, adiponectin), inflammation (C-reactive protein (CRP)), and prostate-specific antigen (PSA). Biomarker changes over time and between arms were analyzed using linear mixed-effects models and intention-to-treat analysis. Results 22 (85%) intervention and 23 (92%) control participants, mean (SD) age of 63.6 (6.6) years, provided two blood samples. Average baseline biomarker values were within expected ranges. Analyses showed no changes within or differences in changes between intervention and control groups from baseline to 16 weeks for any biomarker ( p > 0.05). Conclusions We observed no changes in markers of insulinemia, inflammation, or PSA from a 16-week at-home walking intervention vs. control in individuals with low-risk PCa.

Hooking recreational fishers on sustainable fishing: Consistent psycho-social determinants raise potential for broad scale interventions - Matthew Navarro; Tracey Mahony; Diane Jarvis; Natalie Stoeckl; Francisco Gelves-Gomez; Vanessa M. Adams (Ambio, 2026)
The establishment of marine protected areas with high levels of compliance is a cornerstone of global marine conservation. Previous studies highlight the importance of psycho-social mechanisms (e.g. attitudes, social norms) for driving self-compliance amongst recreational fishers. However, our ability to put these fishery-specific insights into broad-practice requires understanding how transferable they are across locations. In this study, we find that psycho-social determinants of sustainable fishing practices are consistent across three contrasting marine protected areas spanning the Australian continent (separated by up to 3500 km). Intentions to promote sustainable fishing practices were stronger for fishers who were aware of zoning, were positive towards regulations, and whose peers supported sustainable fishing practices. Most of the variability in these factors was linked to intangible fisher characteristics, especially fisher motivations. Consistency across our national sample raises the potential for a national approach to tackling self-compliance of recreational fishers with marine protected area regulations.

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Do some tiger sharks prefer beaches? Insights for shark management from a broad-scale comparative tracking study - Matthew N. McMillan; Adam Barnett; Stacy L. Bierwagen; Tracey B. Scott-Holland; Vinay Udyawer; Matthew Campbell; Richard Fitzpatrick; Nicolas Lubitz; Ingo B. Miller; Leanne M. Currey-Randall (Ocean & Coastal Management, 2026)

The effect of Asparagopsis oil supplementation level on tissue residues and meat quality of Merino sheep fed high- or low-quality basal diets - Charlotte Adam; Emma Doyle; Jillian Dawson; Frances Cowley; Nigel Tomkins; Lewis Kahn; James Preston; Daniel Korir Sitienei; Matthew Tom Harrison; Benjamin W.B. Holman (Small Ruminant Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Assessing recovery and conservation of Australian freshwater fishes with the IUCN Green Status of Species and structured expert elicitation - Maiko L. Lutz; David G. Chapple; Molly K. Grace; Luciano B. Beheregaray; Chris J. Brauer; Iain Ellis; Adam Kerezsy; John D. Koehn; Mark Lintermans; Jarod P. Lyon; Matthew McLellan; Luke Pearce; et al. (Conservation Biology, 2025)
The International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), introduced in 2021, is a global standard of measurement used to assess the level to which a species has recovered (i.e., is viable and providing its ecological function across its entire range). It is also used to evaluate how a species has responded to past conservation actions and the expected conservation gains and recovery potential it would receive in the short‐ and long‐term future. Preliminary application of the GSS method has relied on expert knowledge from individuals or small groups of specialists. However, more accurate and reliable results are likely to be produced by formally eliciting individual judgments from a diverse range of experts, followed by discussion, reevaluation, and synthesis of these judgments. We developed a method in which 2 structured expert elicitation workshops are used to conduct GSS assessments and applied this method to 8 Australian freshwater fish species from the Murray–Darling Basin. We integrated the investigate, discuss, evaluate, aggregate protocol into the GSS methods; experts assessed the species’ IUCN Green Score (percent recovery) in the current state and for 5 other scenarios in the past and future with and without conservation. Four GSS conservation impact metrics were calculated based on the averages of expert judgments. Experts forecasted that impact in the short‐term would be minimal (i.e., conservation gain metric = zero or low) for 5 of the 8 species because targeted and maintained conservation actions are often lacking. In contrast, experts indicated long‐term recovery potential would be considerably higher if implementation of appropriate recovery activities could be sustained (all 8 species had medium or high recovery potential). We concluded that the GSS is well suited to a modified workshop approach because it aims to reduce biases associated with expert judgments and encourages valuable knowledge sharing among experts.

Substantiating chemical groups for read-across using molecular response profiles - Rosemary E. Barnett; Thomas N. Lawson; Claudia Rivetti; Carlos Barata; Mark T.D. Cronin; Silvia Lacorte; Gavin R. Lloyd; Ralf J.M. Weber; Matthew J. Smith; Andrew D. Southam; Adam Biales; Kara Koehrn; et al. (Regulatory Toxicology and Pharmacology, 2025)

Multi-physics simulation–driven assessment of environmental and cost performance in ultra-high performance concrete (UHPC) bridge deck under local climate effects - Jin Fan; Wei Huang; Hao Wang; Matthew P. Adams; Matthew J. Bandelt (Engineering Structures, 2025)

Fate of synthetic fertilizer nitrogen in a maize system depends on dairy manure type: insights from an isotopic tracing field study - Joshua P Mirabella; Adam von Haden; Gregg Sanford; Matthew Ruark; Xia Zhu-Barker (Biology and Fertility of Soils, 2025)
Understanding the fate of fertilizer nitrogen (N) in cropping systems is critical to improving agricultural sustainability and minimizing environmental losses. However, efforts to trace fertilizer N are often complicated by manure application in dairy cropping systems. We used a stable isotope tracing approach to investigate how different manure products influence the fate of synthetic fertilizer N in a Midwestern maize silage system by tracking 15 N-labled ammonium sulfate into crop biomass, soil organic matter fractions (particulate (POM) and mineral associated (MAOM)), and gaseous loss as nitrous oxide (N 2 O). Treatments included unprocessed liquid manure (LM), solid manure derived through chemical (CS) or physical (PS) separation, and a no-manure control (NM), combined with fertilizer rates of 90, 180, and 270 kg N ha −1 . Cumulative N 2 O emissions increased significantly with both manure application and higher fertilizer rates, with PS having lower emissions than LM following fertilizer application. Fertilizer contributed similar proportions to cumulative N 2 O emissions regardless of manure treatment. Total fertilizer N uptake by crops did not differ among manure treatments, but crops took up more fertilizer N at higher fertilizer application rates. Notably, application of CS and PS enhanced fertilizer N retention in the 0–15 cm soil MAOM pool compared to LM and NM. These findings highlight that although manure type does not significantly affect fertilizer N uptake by crops or fertilizer-derived N 2 O emissions, solid manures (i.e., CS and PS) can significantly increase fertilizer N retention in soils, offering potential benefits for long-term soil fertility and reduced N losses.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Delirium in hospitalized COVID-19 patients is associated with dynamic changes in peripheral immune gene expression - Sara C. LaHue; Naoki Takegami; Rubinee Simmasalam; Abiya Baqai; Elena Munoz; Anya Sikri; Thibault du Buisson de Courson; Nilika S. Singhal; Walter Eckalbar; Charles R. Langelier; Carolyn M. Hendrickson; Carolyn S. Calfee; et al. (GeroScience, 2025)
Delirium is a neurologic syndrome characterized by inattention and cognitive impairment frequently encountered in medically ill older adults. As a hallmark of age-related brain vulnerability, delirium offers a clinical model to investigate how peripheral immune responses contribute to acute brain dysfunction. Peripheral inflammation is a key trigger of delirium, but the patient-specific immune responses that drive delirium onset and recovery remain poorly understood. This retrospective cohort study of prospectively collected biospecimens examines RNA sequencing from peripheral blood mononuclear cells of adults hospitalized for COVID-19 to better understand patient-specific factors associated with delirium ( n = 64). Longitudinal transcriptomic analyses highlight persistent immune dysregulation in delirium, marked by increasing expression trajectories of genes linked to innate immune pathways, including complement activation, cytokine production, and monocyte/macrophage recruitment. Genes involved adaptive immunity showed a declining trajectory over time in patients with delirium. Although corticosteroid treatment suppressed some aspects of immune hyperactivation, aberrant responses contributing to delirium were exacerbated. Delirium resolution was characterized by normalization of key transcripts such as CCL2 and innate immune markers. Novel associations with delirium included transcripts related to stress granule assembly and the T cell regulators DUSP2 and KLF10 . Delirium in COVID-19 is associated with distinct and dynamic peripheral immune trajectories that are modulated by corticosteroids. Further understanding these mechanisms has important implications for preventing delirium in older adults. These findings provide novel mechanistic insights with translational relevance for immunomodulatory strategies targeting maladaptive immune responses to prevent or treat delirium in medically ill populations.

Porosity and hydrous alteration of the Martian crust from InSight seismic data - Brigitte Knapmeyer-Endrun; Ludmila Adam; Sebastian Carrasco; Matthew P. Golombek; Doyeon Kim; Martin Knapmeyer; Katarina Miljković; Ana-Catalina Plesa; Nicholas H. Warner; Mark Wieczorek (Physics of the Earth and Planetary Interiors, 2025)

Scale model and ship simulator towing of the IEA 15 MW wind turbine on the UMaine VolturnUS-S platform - Adam Roberts; Frédéric Le Pivert; Saied Kazemi; Tom Tosdevin; Adán López-Santander; Matthew J. Craven; Lars Johanning (Ocean Engineering, 2025)

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Disentangling global geochemical signals from local diagenetic alteration in shallow-water marine carbonates during OAE1a - Matthew D. Nadeau; Jack G. Murphy; Cedric J. Hagen; Ziman Wu; Alliya A. Akhtar; Anne-Sofie Ahm; Daniel A. Stolper; Adam C. Maloof; John A. Higgins (Earth and Planetary Science Letters, 2025)

Comparative Phylogeography of West African Rainforest Frogs Reveals Regional Variation in Refugia Dynamics - Mario Ernst; Daniel M. Portik; Gabriel H. Segniagbeto; Caleb Ofori‐Boateng; Joseph Doumbia; Johannes Penner; N'Goran G. Kouamé; Matthew K. Fujita; Adam D. Leaché; Mozes P. K. Blom; Mark‐Oliver Rödel (Molecular Ecology, 2025)
Understanding how species responded to climatic change in the past can help predict the long‐term implications of contemporary climate change. The Upper Guinean rainforests of West Africa are a global biodiversity hotspot, and it is well documented that climatic fluctuations in the Pleistocene drove the expansion and contraction of rainforest cover in this region. West African slippery frogs, genus Conraua , are rainforest specialists and present an excellent opportunity to study the effects of climate‐driven landscape changes on contemporary phylogeographic patterns and population dynamics. They exclusively inhabit rainforest streams and show little morphological or ecological disparity. We generated a population‐level dataset of genome‐wide restriction site‐associated DNA (RAD) loci for four species spread across Upper Guinea. The observed phylogeographic structure is consistent with previously postulated macro‐ and micro‐refugia. Building on these results, we used demographic modelling to trace demographic trends over time and infer population connectivity patterns. Overall, populations in topographically complex regions, like the Fouta Djallon, showed signatures of long‐term local persistence and milder changes in population size. In contrast, we found more dynamic histories of contraction and expansion in the main Upper Guinean rainforest block. Our findings provide insights into regional biodiversity patterns and show large variation in population responses to climatic fluctuations. This suggests that local environmental factors have played a key role in shaping population dynamics. Such insights are particularly relevant in relatively understudied biodiversity hotspots, such as the Upper Guinean rainforests of West Africa. Our results have implications for conservation management and prioritisation at the species, site, and ecosystem level.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Rapid Ocean Warming Drives Sexually Divergent Habitat Use in a Threatened Predatory Marine Ectotherm - Lucy R. Mead; Adam Piper; David Jiménez Alvarado; Eva Meyers; Joanna Barker; Hector Toledo‐Padilla; Edy Herraiz; Alberto F. Campoamor; Michael Sealey; Maria Belén Caro; Tomàs Bañeras; Charlotte Pike; et al. (Global Change Biology, 2025)
Climate change poses one of the greatest threats to marine ecosystems worldwide, altering physical, chemical, and biological processes at unprecedented rates. Severe impacts on marine species and habitats have been extensively documented, with shifts in phenology, spatial distribution, and migratory behaviour increasingly pervasive. However, there is a lack of species‐specific data examining responses and adaptation to rapid warming and environmental extremes, especially for marine ectotherms. In this study, we investigate the broad‐scale environmental drivers of distribution in a Critically Endangered ectothermic marine predator, the angelshark Squatina squatina , and report on a behavioural anomaly observed in 2022. Between 2018 and 2023, 112 adult S. squatina were tracked using acoustic telemetry in La Graciosa Marine Reserve in the Canary Islands. Relationships between seasonal presence of S. squatina and remotely sensed environmental parameters were examined with Boosted Regression Tree and Generalised Additive Modelling. Major sex differences were found, with female sharks strongly influenced by environmental conditions and particularly sensitive to temperature, with a possible upper thermal threshold close to 22.5°C. Peak sea surface temperature in the study area increased from 22.99°C to 23.81°C, and the number of days above 22.5°C nearly tripled. Absence of females during the 2022 breeding season coincided with widespread thermal anomalies across the Northeast Atlantic Ocean, with unusually high temperatures persisting later into the year. We conclude that this potentially disrupted seasonal thermal cues for S. squatina movement, leading to sexually divergent habitat use. Given the warming projected for this region, thermal thresholds may increasingly be exceeded, and key areas may become inhospitable for female S. squatina , which is of huge concern for this already highly threatened species. These findings highlight the urgency of identifying species‐specific environmental tolerances and incorporating these into conservation so that management remains ecologically relevant in a rapidly warming ocean.

Wastewater surveillance as a tool for understanding West Nile virus transmission and distribution in Oklahoma - Katrin Gaardbo Kuhn; Kristen Shelton; Gilson Sanchez; Richard Zamor; Kyle Bohanan; Matthew Nichols; LeMac’ Morris; Jordan Robert; Adam Austin; Bruce Dart; Blaine Bolding; Phil Maytubby; et al. (Science of The Total Environment, 2025)

Assessment of traditional biosolids disposal methods for biosolids contaminated with Bacillus globigii spores - Adam C. Burdsall; Matthew Magnuson; Jeffrey G. Szabo; J. Lee Heckman (Next Research, 2025)

Thresholding and continuous wavelet transform (CWT) analysis of Ground Penetrating Radar (GPR) data for estimation of potato biomass - Henry Ruiz-Guzman; Tyler Adams; Afolabi Agbona; Matthew Wolfe; Mark Everett; Jean-Francois Chamberland; Dirk B. Hays (Computers and Electronics in Agriculture, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Noise results in lower quality of an important forage fish, the Pacific sand lance, Ammodytes personatus - Nora V. Carlson; Meredith A.V. White; Jose Tavera; Patrick D. O'Hara; Matthew R. Baker; Douglas F. Bertram; Adam Summers; David A. Fifield; Francis Juanes (Marine Pollution Bulletin, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

A generalised sigmoid population growth model with energy dependence: Application to quantify the tipping point for Antarctic shallow seabed algae - Elise Mills; Graeme F. Clark; Matthew J. Simpson; Mark Baird; Matthew P. Adams (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Management and Natural Regeneration in Multiple Ponderosa Pine Forests of the Southwestern United States - Matthew D. Petrie; Robert M. Hubbard; John B. Bradford; Tom E. Kolb; Adam Noel; Daniel R. Schlaepfer; Marisa A. Bowen; Lloyd R. Fuller; W. Keith Moser (Forest Science, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Magma storage and transport beneath the near-rift Fjallgarðar Volcanic Ridge, Northeast Iceland - Noëmi Löw; Sæmundur A. Halldórsson; Christoph Beier; Enikő Bali; Simon Matthews; Guðmundur H. Guðfinnsson; Edward W. Marshall; Jóhann Helgason; Eemu Ranta; Adam Abersteiner; Jaime D. Barnes; Alberto Caracciolo (Contributions to Mineralogy and Petrology, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Comparative performance of selected triploid oysters Crassostrea (Magallana) gigas, produced by chemical induction and mated triploid techniques, to their diploid counterparts - Julien Vignier; Matthew Reardon; Megan Exton; Lizenn Delisle; Anne Rolton; Emmanuel Malpot; Megan Scholtens; Mena Welford; Leonardo Zamora; Natali Delorme; Brendon Dunphy; Serean Adams (Aquaculture, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Creek System and Regional Patterns of Juncus roemerianus Stress and Links to Salt Marsh Loss on the Florida Gulf Coast - Stephanie A. Verhulst; Matthew P. Conlin; Peter N. Adams; Carrie Reinhardt Adams (Wetlands, 2025)

The first fossil longhorn beetles (Coleoptera: Cerambycidae) from Australia - Lachlan J. Hart; Adam Ślipiński; Michael Frese; Tara Djokic; Matthew R. McCurry (The Science of Nature, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

Investigation of long-term pressure on primary packaging materials and a biologic drug product for injection with a novel autoinjector concept - Daniel Primavessy; Max Piening; Adam Nightingale; Heather Jameson; Matthew Latham; James Alexander; Sarah Büttner; Juergen Pfrang; Andreas Zapf; Tom Oakley; Andreas Brutsche; Sigrid Saaler-Reinhardt (Drug Delivery and Translational Research, 2025)
Gerresheimer and Midas Pharma have developed a novel cartridge-based autoinjector concept in which the cartridge as primary packaging is under constant pressure. In this article standard cartridge primary packaging material of five different companies were analyzed for their behavior under long-term pressure. Materials of 3 glass manufacturers and 2 manufacturers for cartridge rubber parts were considered. Within the test program septum stability, septum piercing, glide forces (GF), break-loose forces (BLF), glass breaking as well as a regulatory approved and marketed antibody drug product under pressure were subject to analysis. Under pressure the cartridge septum bulge grew within the first 14 days and then relevantly slowed down. An accelerated study in different atmospheric conditions allowed to extrapolate values for 24 months storage, not showing any signs of decay or problematic septum bulge increase. Pierce forces were in normal ranges and septum rupture could not be observed at the end of 42 days of pressurization. GF and BLF were within acceptable ranges and changes due to pressure could not be observed. Lowest glass breaking pressures at 4922 kPa turned out to be at least 3.5 times higher than pressures used in the autoinjector concept. Degradation of the Adalimumab antibody drug product due to pressure or device fluid pathway could not be observed with size exclusion chromatography, electrophoresis or sub-visible particles tested as a release testing in a GMP setting. Graphical Abstract

Ecological biogeography of maize rhizosphere underpins spatial variation of bacteriome and phylotypes for maize productivity - Tawakalit Modupe Momoh-Salami; Nwanneka Marie Akinyemi; Ganiyu Oladunjoye Oyetibo; Godwin Anjorin Ajiboye; Luqman Ayodeji Adams; Liasu Adebayo Ogunkanmi; Matthew Olusoji Ilori (Applied Soil Ecology, 2025)

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Associations between physical activity, brain health, cognitive function, and circulating GPLD1 in healthy older (65–85 years) individuals - Kara L. Marlatt; Adam C. Lowe; Guillermo Sanchez-Delgado; Robbie A. Beyl; Matthew K. Viverito; Jeffrey N. Keller; Owen T. Carmichael; Eric Ravussin (GeroScience, 2025)

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

Intraspecific interactions and thermal refuge availability interactively influence ectotherm thermoregulation but not energy dynamics - David R. Adams; Matthew E. Gifford (Journal of Thermal Biology, 2025)

Collaborating with Marine Birds to Monitor the Physical Environment Within Coastal Marine Protected Areas - Rachael Orben; Adam Peck-Richardson; Alexa Piggott; James Lerczak; Greg Wilson; Jessica Garwood; Xiaohui Liu; Sabir Muzaffar; Alexa Foster; Humood Naser; Mohamed AlMusallami; Tycho Anker-Nilssen; et al. (Oceanography, 2025)
Animal telemetry is maturing into a viable method for observing the ocean as it can be used to monitor both environmental conditions and biological metrics along the movement trajectories of marine animals. As part of the Cormorant Oceanography Project, we have augmented a biologging tag with an external fast response temperature sensor to collect ocean temperature profiles from the backs of foraging marine birds. Cormorants dive between 50 and 250+ times a day to forage for prey so they can provide hard-to-match temporal and spatial coverage of coastal ocean conditions within their foraging areas. We process tag measurements to obtain fundamental oceanographic data (e.g., temperature profiles, bottom soundings, surface current measurements). Together, we have tracked 17 marine bird species (including two Spheniscus penguins spp. and a sea duck), originating from 17 countries and foraging along the edges of all major oceans. Tagged birds’ distribution included 191 MPAs in 26 countries, offering a unique ocean monitoring method to complement more widely used methods.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Environmental fluoxetine promotes skin cell proliferation and wound healing - Quentin Rodriguez-Barucg; Angel A. Garcia; Belen Garcia-Merino; Tomilayo Akinmola; Temisanren Okotie-Eboh; Thomas Francis; Eugenio Bringas; Inmaculada Ortiz; Mark A. Wade; Adam Dowle; Domino A. Joyce; Matthew J. Hardman; et al. (Environmental Pollution, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Fawn bedsite selection by a large ungulate living in a peri-urban area - Kimberly Conteddu; Katie Wilson; Bawan Amin; Srivats Chari; Amy Haigh; Laura L. Griffin; Matthew Quinn; Andrew Ryan; Adam F. Smith; Simone Ciuti (European Journal of Wildlife Research, 2024)

Climate Change and the Emergence of No‐Analog Forest Assemblages in North America - Andrew V. Gougherty; Anantha M. Prasad; Matthew P. Peters; Stephen N. Matthews; Bryce T. Adams (Global Change Biology, 2024)
Future climate change is expected to result in tree species shifting their geographic distributions in ways that could reorganize species into assemblages with no contemporary analog. These projected no‐analog forests raise concern as their ecological function could similarly shift, which may challenge established conservation and management efforts. Here, we implement a community‐level modelling approach to identify the key climatic and topographic drivers of forest composition in North America, and then use these models to predict the distribution of “disappearing” and “novel” forest assemblages in future climate. We applied this modelling technique to both the taxonomic and phylogenetic composition of forest trees, to identify where species turnover may be greatest, and whether species are likely to be replaced with close relatives. Our work shows that approximately 11.9% of contemporary North American forests have low predicted similarity to future forests, and 26.2% of future forests could be compositionally novel compared with contemporary forests, but there was substantial geographic variability in the magnitude of these metrics across the continent. High‐elevation regions in the west tend to be nearest to their closest compositional analog, suggesting these regions may be most likely to realize the future predicted composition. This work provides a new approach to understanding how forest composition may shift in future climates in a way that avoids the need for individual species predictions and extends climate‐matching approaches with meaningful biological data.

Comparative lifespan and healthspan of nonhuman primate species common to biomedical research - Hillary F. Huber; Hannah C. Ainsworth; Ellen E. Quillen; Adam Salmon; Corinna Ross; Adinda D. Azhar; Karen Bales; Michele A. Basso; Kristine Coleman; Ricki Colman; Huda S. Darusman; William Hopkins; et al. (GeroScience, 2024)

Modelling the microscale spatial distribution of urban air temperature in suburban sprawl - Scarlett B. Rakowska; Matthew D. Adams (Urban Climate, 2024)

Wild pigs influence tropical forest soil microbial communities in a forest-agriculture mosaic landscape - Francis Q. Brearley; Hokyung Song; Binu M. Tripathi; Ke Dong; Noraziah M. Zin; Abdul Rahim Abdul Rachman; Kalan Ickes; Jonathan M. Adams; Matthew S. Luskin (Forest Ecology and Management, 2024)

The Current State of Biotransformation Science – Industry Survey of In Vitro and In Vivo Practices, Clinical Translation, and Future Trends - John P. Savaryn; Kevin Coe; Matthew A. Cerny; Kevin Colizza; Patricia Moliner; Lloyd King; Bin Ma; Jim Atherton; Adam Auclair; Mark T. Cancilla; Marsha Eno; Ulrik Jurva; et al. (Pharmaceutical Research, 2024)

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Evolutionary relationships and fine-scale geographic structuring in the temperate percichthyid genus Gadopsis (blackfishes) to support fisheries and conservation management - Matthew A. Campbell; Michael P. Hammer; Mark Adams; Tarmo A. Raadik; Peter J. Unmack (Molecular Phylogenetics and Evolution, 2024)

Sustainable reinforced concrete design: The role of ultra-high performance concrete (UHPC) in life-cycle structural performance and environmental impacts - Jin Fan; Yi Shao; Matthew J. Bandelt; Matthew P. Adams; Claudia P. Ostertag (Engineering Structures, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Transcriptomic analyses during development reveal mechanisms of integument structuring and color production - Adam M. M. Stuckert; Layla Freeborn; Kimberly A. Howell; Yusan Yang; Rasmus Nielsen; Corinne Richards-Zawacki; Matthew D. MacManes (Evolutionary Ecology, 2024)
Skin coloration and patterning play a key role in animal survival and reproduction. As a result, color phenotypes have generated intense research interest. In aposematic species, color phenotypes can be important in avoiding predation and in mate choice. However, we still know little about the underlying genetic mechanisms of color production, particularly outside of a few model organisms. Here we seek to understand the genetic mechanisms underlying the production of different colors and how these undergo shifting expression patterns throughout development. To answer this, we examine gene expression of two different color patches(yellow and green) in a developmental time series from young tadpoles through adults in the poison frog Oophaga pumilio. We identified six genes that were differentially expressed between color patches in every developmental stage ( casq1, hand2, myh8, prva, tbx3, and zic1). Of these, hand2, myh8, tbx3, and zic1 have either been identified or implicated as important in coloration in other taxa. Casq1 and prva buffer Ca 2+ and are a Ca 2+ transporter, respectively, and may play a role in preventing autotoxicity to pumiliotoxins, which inhibit Ca 2+ -ATPase activity. We identify further candidate genes (e.g., adh, aldh1a2, asip, lef1, mc1r, tyr, tyrp1, xdh ), and identify a suite of hub genes that likely play a key role in integumental reorganization during development (e.g., collagen type I–IV genes, lysyl oxidases) which may also affect coloration via structural organization of chromatophores that contribute to color and pattern. Overall, we identify the putative role of a suite of candidate genes in the production of different color types in a polytypic, aposematic species.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Calcification increases carbon supply, photosynthesis, and growth in a globally distributed coccolithophore - Austin R. Grubb; Christopher T. Johns; Matthew G. Hayden; Adam V. Subhas; Kimberlee Thamatrakoln; Kay D. Bidle (Limnology and Oceanography, 2024)
Coccolithophores fix organic carbon and produce calcite plates (coccoliths) that ballast organic matter and facilitate carbon export. Photosynthesis consumes carbon dioxide, while calcification produces it, raising questions about whether coccolithophores are a net sink or source of carbon. We characterized the physiology of calcified and noncalcified (“naked”) phenotypes of Emiliania huxleyi (CCMP374) and investigated the relationship between calcification and photosynthesis across a gradient of light (25–2000 μ mol photons m −2 s −1 ) spanning the euphotic zone. Growth and photophysiological parameters increased with light until reaching a mid‐light (150 μ mol photons m −2 s −1 ) maximum for both phenotypes. Calcified cells were characterized by enhanced photophysiology and less photoinhibition. Further, enhanced bicarbonate transport in calcified cells led to higher rates of particulate organic carbon fixation and growth compared to naked cells at mid‐light to high light (150–2000 μ mol photons m −2 s −1 ). Coccolith production was similarly high at mid and high light, but the rate of coccolith shedding was >3‐fold lower at high‐light (1.2 vs. 0.35 coccoliths cell −1 h −1 ). The cellular mechanims(s) of this differential shedding remain unknown and underly light‐related controls on coccosphere maintenance. Our data suggest coccoliths shade cells at high light and that enhanced bicarbonate transport associated with calcification increases internal carbon supplies available for organic carbon fixation.

Next generation risk assessment for occupational chemical safety – A real world example with sodium-2-hydroxyethane sulfonate - Adam Wood; Catherine Breffa; Caroline Chaine; Richard Cubberley; Matthew Dent; Joachim Eichhorn; Susann Fayyaz; Fabian A. Grimm; Jade Houghton; Reiko Kiwamoto; Predrag Kukic; MoungSook Lee; et al. (Toxicology, 2024)

Routing optimisation for towing a floating offshore wind turbine under weather constraints - Frédéric Le Pivert; Adán López-Santander; Matthew J. Craven; Adam Roberts (Ocean Engineering, 2024)

The 3D response of a large-scale masonry arch bridge – Part II: Performance at failure - Bowen Liu; Vasilis Sarhosis; Adam D. Booth; Matthew Gilbert (Engineering Structures, 2024)

The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2024)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which species share a conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which mimicry is produced in poison frogs. We assembled a 6.02‐Gbp genome with a contig N50 of 310 Kbp, a scaffold N50 of 390 Kbp and 85% of expected tetrapod genes. We leveraged this genome to conduct gene expression analyses throughout development of four colour morphs of Ranitomeya imitator and two colour morphs from both R. fantastica and R. variabilis which R. imitator mimics. We identified a large number of pigmentation and patterning genes differentially expressed throughout development, many of them related to melanophores/melanin, iridophore development and guanine synthesis. We also identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species, and identify several plausible candidates for colouration in vertebrates (e.g. cd36 , ep‐cadherin and perlwapin ). Finally, we hypothesise that keratin genes (e.g. krt8 ) are important for producing different structural colours within these frogs.

Leveraging AI to improve evidence synthesis in conservation - Oded Berger-Tal; Bob B.M. Wong; Carrie Ann Adams; Daniel T. Blumstein; Ulrika Candolin; Matthew J. Gibson; Alison L. Greggor; Malgorzata Lagisz; Biljana Macura; Catherine J. Price; Breanna J. Putman; Lysanne Snijders; et al. (Trends in Ecology & Evolution, 2024)

A meta-analysis of the carcinogenic effects of particulate matter and polycyclic aromatic hydrocarbons - Irtaqa Arif; Matthew D. Adams; Marc T.J. Johnson (Environmental Pollution, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Parsing the toxicity paradox: Composition and duration of exposure alter predicted oil spill effects by orders of magnitude - Deborah P. French-McCay; Hilary J. Robinson; Julie E. Adams; Matthew A. Frediani; Matthew J. Murphy; Cheryl Morse; Melissa Gloekler; Thomas F. Parkerton (Marine Pollution Bulletin, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Updated review of the conservation status of Nubian giraffe (Giraffa camelopardalis camelopardalis) in Kenya - Arthur B. Muneza; Janet S. Kavutha; Matthew W. Muruana; Timothy Ikime; Linus Kariuki; Isaac Lekolool; Stephanie Fennessy; Alice Bett; Adams K. Kipchumba; Emmanuel Ngumbi; Julian Fennessy (Biodiversity and Conservation, 2024)

Out of sight, but not out of season: Nitrifier distributions and population dynamics in a large oligotrophic lake - Logan M. Peoples; Miranda H. Seixas; Kate A. Evans; Evan M. Bilbrey; John R. Ranieri; Tyler H. Tappenbeck; John E. Dore; Adam Baumann; Matthew J. Church (Environmental Microbiology, 2024)
Nitrification is an important control on the form and distribution of nitrogen in freshwater ecosystems. However, the seasonality of nitrogen pools and the diversity of organisms catalyzing this process have not been well documented in oligotrophic lakes. Here, we show that nitrogen pools and nitrifying organisms in Flathead Lake are temporally and vertically dynamic, with nitrifiers displaying specific preferences depending on the season. While the ammonia‐oxidizing bacteria (AOB) Nitrosomonadaceae and nitrite‐oxidizing bacteria (NOB) Nitrotoga dominate at depth in the summer, the ammonia‐oxidizing archaea (AOA) Nitrososphaerota and NOB Nitrospirota become abundant in the winter. Given clear seasonality in ammonium, with higher concentrations during the summer, we hypothesize that the succession between these two nitrifying groups may be due to nitrogen affinity, with AOB more competitive when ammonia concentrations are higher and AOA when they are lower. Nitrifiers in Flathead Lake share more than 99% average nucleotide identity with those reported in other North American lakes but are distinct from those in Europe and Asia, indicating a role for geographic isolation as a factor controlling speciation among nitrifiers. Our study shows there are seasonal shifts in nitrogen pools and nitrifying populations, highlighting the dynamic spatial and temporal nature of nitrogen cycling in freshwater ecosystems.

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

Shallow carbonate geochemistry in the Bahamas since the last interglacial period - Stacey Edmonsond; Matthew D. Nadeau; Andrew C. Turner; Ziman Wu; Emily C. Geyman; Anne-Sofie C. Ahm; Blake Dyer; Sergey Oleynik; David McGee; Daniel A. Stolper; John A. Higgins; Adam C. Maloof (Earth and Planetary Science Letters, 2024)

Trace element chemistry and strontium isotope ratios of atmospheric particulate matter reveal air quality impacts from mineral dust, urban pollution, and fireworks in the Wasatch Front, Utah, USA - Micah J. Marcy; Gregory T. Carling; Alyssa N. Thompson; Barry R. Bickmore; Stephen T. Nelson; Kevin A. Rey; Diego P. Fernandez; Matthew Heiner; Bradley R. Adams (Applied Geochemistry, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Numerical modeling of plunging jets of brine: Mass transport and implications for desalination plant outfalls - Matthew T. Flavin; Jenifer Fernandes; Rawan AlQabandi; Eric Adams; Jongyoon Han; Bader Al-Anzi (Desalination, 2023)

Estimation of daily NO2 with explainable machine learning model in China, 2007–2020 - Yanchuan Shao; Wei Zhao; Riyang Liu; Jianxun Yang; Miaomiao Liu; Wen Fang; Litiao Hu; Matthew Adams; Jun Bi; Zongwei Ma (Atmospheric Environment, 2023)

Reproductive biology of male common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2023)
Reproductive parameters were assessed in 64 male common dolphins ( Delphinus delphis ) examined post-mortem from strandings and bycatch in New Zealand between 1999 and 2020. The stages of male sexual maturation were assessed using morphological measurements and histological examination of testicular tissue. Age was determined via growth layer groups (GLGs) in teeth. The average age (ASM) and length (LSM) at attainment of sexual maturity were estimated to be 8.8 years and 198.3 cm, respectively. Individual variation in ASM (7.5–10 years) and LSM (190–220 cm) was observed in New Zealand common dolphins. However, on average, sexual maturity was attained at a similar length but at a marginally younger age (< 1 year) in New Zealand compared to populations in the Northern Hemisphere. All testicular variables proved better predictors of sexual maturity compared to demographic variables (age and total body length), with combined testes weight the best outright predictor of sexual maturity. Reproductive seasonality was observed in male common dolphins, with a significant increase in combined testes weight in austral summer. This aligns with most other studied populations, where seasonality in reproduction is typically observed. Given the known anthropogenic impacts on New Zealand common dolphins, we recommend that these findings be used as a baseline from which to monitor population-level changes as part of conservation management efforts.

Exploring the internal textures and physical properties of digitate sinter in hot springs: Implications for remote sampling on Mars - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Ang; Steve Matthews; Steven W. Ruff; Ashok Meghwal; Ludmila Adam; Niamh Galligan; Thomas Loho (Planetary and Space Science, 2023)

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Total water level controls on the trajectory of dune toe retreat - Matthew P. Conlin; Nicholas Cohn; Peter N. Adams (Geomorphology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Acute and chronic toxicity of manganese to tropical adult coral (Acropora millepora) to support the derivation of marine manganese water quality guideline values - Lisa A. Golding; Monique T. Binet; Merrin S. Adams; Justin Hochen; Craig A. Humphrey; Gwilym A.V. Price; Amanda J. Reichelt-Brushett; Matthew Salmon; Jenny L. Stauber (Marine Pollution Bulletin, 2023)

Fruit availability and human disturbance influence forest elephant group size - Amelia C. Meier; Stephanie Bourgeois; Evan Adams; Hugues Bikang; Liam Jasperse-Sjolander; Matthew Lewis; Juliana Masseloux; Dana J. Morin; John R. Poulsen (Animal Behaviour, 2023)

A DNA-barcode biodiversity standard analysis method (DNA-BSAM) reveals a large variance in the effect of a range of biological, chemical and physical soil management interventions at different sites, but location is one of the most important aspects determining the nature of agricultural soil microbiology - Matías Fernández-Huarte; John G. Elphinstone; Ian P. Adams; Joana G. Vicente; Anne Bhogal; Christine A. Watson; Francois Dussart; Elizabeth A. Stockdale; John Walshaw; Sam McGreig; Robert W. Simmons; Lucie Mašková; et al. (Soil Biology and Biochemistry, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Characterisation of two snake toxin-targeting human monoclonal immunoglobulin G antibodies expressed in tobacco plants - Catherine M. Moore; Anne Ljungars; Matthew J. Paul; Camilla Holst Dahl; Shirin Ahmadi; Anna Christina Adams; Lise Marie Grav; Sanne Schoffelen; Bjørn Gunnar Voldborg; Andreas Hougaard Laustsen; Julian K-C Ma (Toxicon, 2023)

Metagenetics of fairy rings reveals complex and variable soil fungal communities - Siyu XU; Ke DONG; Sangseob LEE; Matthew Chidozie OGWU; Sainbileg UNDRAKHBOLD; Dharmesh SINGH; Dagvatseren ARIUNZAYA; Orsoo ENKHMANDAL; Laura A. SPENCE; Anarmaa SHARKHUU; Brenda B. CASPER; Jonathan M. ADAMS; et al. (Pedosphere, 2023)

Ex Vivo Immunomodulatory Effects of Lactobacillus-, Lacticaseibacillus-, and Bifidobacterium-Containing Synbiotics on Human Peripheral Blood Mononuclear Cells and Monocyte-Derived Dendritic Cells in the Context of Grass Pollen Allergy - Alexander Heldner; Matthew D. Heath; Benjamin Schnautz; Sebastian Kotz; Adam Chaker; Matthias F. Kramer; Constanze A. Jakwerth; Ulrich M. Zissler; Carsten B. Schmidt-Weber; Simon Blank (Probiotics and Antimicrobial Proteins, 2023)
Sensing of the intestinal microbiota by the host immune system is important to induce protective immune responses. Hence, modification of the gut microbiota might be able to prevent or treat allergies, mediated by proinflammatory Th2 immune responses. The aim was to investigate the ex vivo immunomodulatory effects of the synbiotics Pollagen® and Kallergen®, containing the probiotic bacterial strains Lactobacillus , Lacticaseibacillus and Bifidobacterium , in the context of grass pollen allergy. Peripheral blood mononuclear cells (PBMCs) from grass pollen–allergic patients and healthy controls were stimulated with grass pollen extract (GPE) and synbiotics and Gata3 expression and cytokine secretion analyzed. Monocyte-derived dendritic cells (MoDCs) cells were matured in the presence of GPE and synbiotics, co-cultured with autologous naïve T cells and maturation markers and cytokine secretion analyzed. GPE stimulation of PBMCs from grass pollen–allergic patients resulted in a significant higher production of the Th2 cytokines IL-4, IL-5, IL-9 and IL-13 compared to healthy controls. Gata3 + CD4 + T cell induction was independent of the allergic status. The synbiotics promoted IL-10 and IFN-γ secretion and downregulated the GPE-induced Th2-like phenotype. Co-culturing naïve T cells with MoDCs, matured in the presence of GPE and synbiotics, shifted the GPE-induced Th2 cytokine release towards Th1-Th17-promoting conditions in allergic subjects. The investigated synbiotics are effective in downregulating the GPE-induced Th2 immune response in PBMCs from grass pollen–allergic patients as well as in autologous MoDC-T cell stimulation assays. In addition to increased IL-10 release, the data indicates a shift from a Th2- to a more Th1- and Th17-like phenotype.

Expert consensus on neurodevelopmental outcomes in pregnancy pharmacovigilance studies - Rebecca Bromley; Miriam Bickle Graz; Matthew Bluett-Duncan; Christina Chambers; Per Damkier; Kim Dietrich; Helen Dolk; Kimberley Grant; Sarah Mattson; Kim Meador; Hedvig Nordeng; Tim Oberlander; et al. (Neurotoxicology and Teratology, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Historical Plant Sales ( HPS ) database: Documenting the spatiotemporal history of plant sales in the conterminous U.S. - Matthew E. Fertakos; Evelyn M. Beaury; Neil R. Ford; Nicole L. Kinlock; Denise W. Adams; Bethany A. Bradley (Ecology, 2023)
Historical horticultural plant sales influence native and nonnative species assemblages in contemporary ecosystems. Over half of nonnative, invasive plants naturalized in the United States were introduced as ornamentals, and the spatial and temporal patterns of early introduction undoubtedly influence current invasion ecology. While thousands of digitized nursery catalogs documenting these introductions are publicly available, they have not been standardized in a single database. To fill this gap, we obtained the names of all plant taxa (species, subspecies, and varieties) present in the Biodiversity Heritage Library's (BHL) Seed and Nursery Catalog Collection. We then searched the BHL database for these names and downloaded all available records. We combined BHL records with data from an encyclopedia of heirloom ornamental plants to create a single database of historical nursery sales in the US. Each record represents an individual taxon offered for sale at an individual time in a specific nursery's catalog. We standardized records to the current World Flora Online ( http://worldfloraonline.org ) accepted taxonomy and appended accepted USDA code, growth habit, and introduction status. We also appended whether taxa were reported as invasive in the Global Plant Invaders (GPI) data set or the Global Invasive Species Database (GISD) or regulated in the conterminous US. Lastly, we geocoded all reported publication locations. The data set contains 2,445,875 records from nurseries in at least 2795 unique locations, with the majority of catalogs published between 1890 and 1950. Nurseries were located in all conterminous states but were concentrated in the eastern US and California. We identified 19,140 unique horticultural taxa, of which 8642 matched taxa in the USDA Plants database. The USDA Plants database is limited to native and naturalized taxa in the US. Native or introduced status was listed in USDA Plants for 7018 of included taxa, while 1642 had an unknown status. The remaining 10,498 taxa are not naturalized according to USDA Plants or are of varieties of native and introduced taxa that did not match USDA Plants taxonomy. The majority of taxa in the Historical Plant Sales (HPS) database with an identified status are native (65.5%; 4596 of 7018 taxa), of which 393 taxa are reported as invasive outside of the US. Of the 2381 introduced taxa, 1103 (46.3%) are reported as invasive somewhere globally. Despite a richer pool of native taxa, most cataloged plant records with an identified status were of introduced taxa (54.1%; 1,045,684 of 1,933,925 records). Plants reported as invasive somewhere globally comprised a large portion of records with an identified status (38.7%; 747,953 of 1,933,925 records) underscoring the large role of ornamental introductions in facilitating plant invasions. The HPS database provides a consolidated and standardized perspective on the history of native, introduced, and invasive plant sales in the US. We release these data into the public domain under a Creative Commons Zero license waiver ( https://creativecommons.org/share-your-work/publicdomain/cc0/ ). Individuals who use these data for publication may cite the associated data paper.

Examining the effects of green space accessibility on school performance for 3421 elementary schools - Scarlett B. Rakowska; Kerstyn L. Lutz; Weeberb J. Réquia; Matthew D. Adams (Landscape and Urban Planning, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Species‐specific acclimatization capacity of key traits explains global vertical distribution of seagrass species - Mario Minguito‐Frutos; Jordi Boada; Jordi F. Pagès; Candela Marco‐Méndez; Rohan Arthur; Matthew P. Adams; Teresa Alcoverro (Global Ecology and Biogeography, 2023)
Aim The global vertical depth distribution of seagrass species remains poorly understood. Locally, the abundance and distribution of seagrasses is determined by light penetration, but at global levels each seagrass species has very distinct maximum distributional depth ranges, indicating that plant‐associated traits must also influence their specific depth ranges. Seagrass‐specific attributes, such as plant size or architecture, growth or reproductive strategy and their physiological and/or morphological acclimatization potential, have been suggested to be responsible for this variety of vertical distributions. We investigate here whether these species‐specific traits drive differences in the global maximum vertical distribution of seagrasses. Location Global. Time period Publications between 1982 and 2020. Major taxa studied Seagrasses (order Alismatales). Methods We tested whether the species‐specific maximum vertical distribution of seagrasses can be predicted by (1) their rhizome diameter (a proxy for plant size); (2) their functional resilience (growth/reproductive strategy); or (3) their acclimatization capacity. For the last aspect, we used a systematic review followed by meta‐analytical approaches to select key seagrass traits that could potentially acclimatize to extreme light ranges across different seagrasses. Results We found that vertical distribution is best explained by the species‐specific acclimatization capacity of various seagrass traits, including saturation irradiance (physiological trait), leaves per shoot (morphological trait) and above‐ground biomass (structural trait). In contrast, our results indicate no predictive power of seagrass size or growth/reproductive strategy on the vertical distribution of seagrasses. Main conclusions Across the globe, the ability of seagrass species to thrive at a wide range of depths is strongly linked to the species‐specific acclimatization capacity of key traits at different organizational levels.

The impact of wildfires on air pollution and health across land use categories in Brazil over a 16-year period - Igor Cobelo; Francisco Jablinski Castelhano; Rafael Borge; Henrique L. Roig; Matthew Adams; Heresh Amini; Petros Koutrakis; Weeberb J. Réquia (Environmental Research, 2023)

TALKS: A systematic framework for resolving model-data discrepancies - Maria P. Vilas; Felix Egger; Matthew P. Adams; Holger R. Maier; Barbara Robson; Jonathan Ferrer Mestres; Lachlan Stewart; Paul Maxwell; Katherine R. O'Brien (Environmental Modelling & Software, 2023)

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Laboratory safety evaluation of lokivetmab, a canine anti-interleukin-31 monoclonal antibody, in dogs - Matthew Krautmann; Rodney R. Walters; Vickie L. King; Kevin Esch; Sean P. Mahabir; Andrea Gonzales; Paul J. Dominowski; Laurel Sly; Duncan Mwangi; Dennis L. Foss; Sharath Rai; James E. Messamore; et al. (Veterinary Immunology and Immunopathology, 2023)

Stochasticity dominates assembly processes of soil nematode metacommunities on three Asian mountains - Shuqi ZOU; Jonathan ADAMS; Zhi YU; Nan LI; Dorsaf KERFAHI; Binu TRIPATHI; Changbae LEE; Teng YANG; Itumeleng MOROENYANE; Xing CHEN; Jinsoo KIM; Hyun Jeong KWAK; et al. (Pedosphere, 2023)

MOO-GAPS: A multi-objective optimization model for global animal production and sustainability - Adam C. Castonguay; Stephen Polasky; Matthew H. Holden; Mario Herrero; Jinfeng Chang; Daniel Mason-D’Croz; Cecile Godde; Katie Lee; Brett A. Bryan; James Gerber; Edward T. Game; Eve McDonald-Madden (Journal of Cleaner Production, 2023)

Shifts in bowhead whale distribution, behavior, and condition following rapid sea ice change in the Bering sea - John J. Citta; Greg A. Breed; Stephen R. Okkonen; Matthew L. Druckenmiller; Lori Quakenbush; John C. George; Billy Adams; Wieslaw Maslowski; Robert Osinski; Justin Olnes; Ellen V. Lea; Robert Suydam (Continental Shelf Research, 2023)

Spatiotemporal distributions of mammals occurring in an agro‐prairie ecosystem - Gabriela Palomo‐Munoz; Ty J. Werdel; Colleen W. Piper; Matthew S. Peek; Andrew M. Ricketts; Adam A. Ahlers (Ecology, 2023)
Anthropogenic activities since the European colonization of the North American Great Plains have drastically altered landscape composition and configuration, subsequently affecting native biodiversity. These contemporary human‐modified landscapes may affect mammal species' distributions, diel activity patterns, habitat use, and interspecific interactions, though a better understanding of these effects on mammals occurring in remaining prairie landscapes is needed. To fill this gap, we surveyed 381 randomly selected sites in 2018, 2019, and 2020 using motion‐sensing camera traps across the western part of the US state of Kansas (7,160,077 ha). Sites were separated by ≥2 km ( = 8.16 km, SD = 3.61), and cameras were secured to a metal post 40 cm above ground and randomly oriented toward the north or south. We placed an olfactory attractant (mixture of skunk essence and petroleum jelly) on a wooden stake 3 m in front of each camera. Cameras were in place at each site for 28 consecutive days for each year. We manually identified all mammal species detected at each site, collating these data into a database that included taxonomic information for 14 families of mammals (Antilocapridae, Bovidae, Canidae, Cervidae, Cricetidae, Dasypodidae, Didelphidae, Erethizontidae, Felidae, Heteromyidae, Leporidae, Mephitidae, Mustelidae, Procyonidae, Sciuridae, and Muridae) comprising 28 total species. We recorded 31,178 mammal photographs (nonindependent events) over 27,954 camera trap nights during 2018 ( n = 10,351), 2019 ( n = 9478), and 2020 ( n = 8125). Additionally, we included the time and date of each photocapture. Moreover, we gathered survey‐specific data useful for modeling species‐specific detection along with site‐level habitat composition data taken at each site each year. These data will be useful for examining habitat use, species distributions, diel activity patterns, and spatiotemporal interactions between species and across guilds of mammals occurring in a rapidly changing agro‐prairie ecosystem. There are no copyright restrictions, but we ask researchers to cite this paper when using these data for publication.

Digestibility of bacterial protein by Atlantic salmon (Salmo salar) is affected by both inclusion level and acclimation time - Brett Glencross; Pedro Muñoz-Lopez; Chessor Matthew; Simon MacKenzie; Adam Powell; Matt Longshaw; Allan LeBlanc (Aquaculture, 2023)

Distribution patterns and influencing factors of population exposure risk to particulate matters based on cell phone signaling data - Chuyi Zhang; Yuanman Hu; Matthew D. Adams; Rencang Bu; Zaiping Xiong; Miao Liu; Yan Du; Binglun Li; Chunlin Li (Sustainable Cities and Society, 2023)

Corrigendum to “The impact of long-term weather changes on air quality in Brazil” [J. Atmos. Environ. 283 (2022) 119182] - Francisco Jablinski Castelhano; Ana Clara Neme Pedroso; Igor Cobelo; Rafael Borge; Henrique L. Roig; Matthew Adams; Heresh Amini; Petros Koutrakis; Weeberb J. Réquia (Atmospheric Environment, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

Leaching composition and associated microbial community of recycled concrete aggregate (RCA) - Maedeh Soleimanifar; Anuruddha Jayasuriya; Matthew P. Adams; Lucia Rodriguez-Freire (Journal of Hazardous Materials, 2023)

Strategic model reduction by analysing model sloppiness: A case study in coral calcification - Sarah A. Vollert; Christopher Drovandi; Gloria M. Monsalve-Bravo; Matthew P. Adams (Environmental Modelling & Software, 2023)

Strategic grassland conservation for swift foxes in multi-use landscapes - Ty J. Werdel; Colleen W. Piper; Andrew M. Ricketts; Matthew S. Peek; Dan S. Sullins; Adam A. Ahlers (Biological Conservation, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Reproductive biology of female common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2022)
Reproductive biology was assessed in 106 female common dolphins ( Delphinus delphis ) examined post-mortem from stranding and bycatch events along the New Zealand coastline between 1997 and 2019. The average age (ASM) and length (LSM) at sexual maturity was estimated at 7.5 years and 183.5 cm, respectively. The total number of corpora in mature individuals increased with age and appeared to persist throughout life. Ovarian asymmetry was apparent, with the left ovary displaying higher rates of ovulation, and a maximum of 19 corpora recorded for a 24-year-old female. The estimated ovulation and annual pregnancy rates for mature females were 0.39 year −1 and 30%, respectively. Conception and calving occurred year-round, with a weak seasonal increase observed in late austral spring and early austral summer. As these data did not clearly show whether seasonality was present, the gestation, lactation, and resting periods were calculated as either 12.6 or 12.8 months based on the presence/absence of seasonality, respectively. Similarly, calving interval ranged from 3.15 to 3.2 years, depending upon whether seasonality was considered. The estimated LSM of the New Zealand population aligns with other populations globally, although the estimated ASM is younger by approximately 6 months. Other reproductive parameters align with Northern Hemisphere populations, although demonstrate variation, which may reflect adaptations to local conditions such as water temperature and prey availability. As the species is subject to anthropogenic impacts including pollution and bycatch, we suggest our findings be used as a baseline with which to monitor trends in population parameters.

Combining acoustic telemetry with a mechanistic model to investigate characteristics unique to successful Atlantic salmon smolt migrants through a standing body of water - Jessie Lilly; Hannele M. Honkanen; Joseph M. McCallum; Matthew Newton; David M. Bailey; Colin E. Adams (Environmental Biology of Fishes, 2022)
The Atlantic salmon, Salmo salar Linnaeus 1758, is a charismatic, anadromous species that has faced dramatic declines throughout its range. There is currently a lack of information on the effect of free-standing bodies of water on a key life event, sea migration, for the species. This study extends our understanding in this area by combining acoustic telemetry with a correlated random walk model to try to examine potential morphological and behavioural factors that differentiate successful from unsuccessful migrants through Scotland’s largest lake. Consistent with other studies, we found that smolts experienced a high rate of mortality in the lake (~ 43%), with approximately 14% potentially predated upon by birds and 4% by Northern pike. Migration speed in the lake was slow (the mean minimum movement speed between centres of activity was 0.13 m/s), and pathways frequently deviated away from the outlet river. There was no evidence of a morphological or behavioural trait or migratory pathway that distinguished successful from unsuccessful smolts. This suggests that migration movement direction in the main body of Loch Lomond appeared to be random. This was further supported by the output of a correlated random walk model which closely resembled the pathway and migration speed and distance patterns displayed by successful migrants. However, once successful smolts came within ~2 km of the lake exit, a high proportion remained in this region prior to entering the River Leven. We suggest that this “goldilocks zone” is where directional cues become apparent to migrating fish. Future studies should combine random walk models with environmental variables to determine if external factors are driving the apparently random movement patterns exhibited by smolts in lakes.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

Concussion Prone Scenarios: A Multi-Dimensional Exploration in Impact Directions, Brain Morphology, and Network Architectures Using Computational Models - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Erin D. Anderson; Matthew B. Panzer; David F. Meaney (Annals of Biomedical Engineering, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Lack of a Zn/Co substitution ability in the polar diatom Chaetoceros neogracile RS19 - Riss M. Kellogg; Dawn M. Moran; Matthew R. McIlvin; Adam V. Subhas; Andrew E. Allen; Mak A. Saito (Limnology and Oceanography, 2022)
Functional substitution of the essential trace metals zinc (Zn) and cobalt (Co) within metalloenzymes has been well documented in marine diatoms and is known to be prevalent among varying genera and species. In contrast to the majority of species studied to date, we find that the polar diatom Chaetoceros neogracile RS19, originally isolated from the Ross Sea, Antarctica, has a Zn requirement that cannot be met by Co and thus does not demonstrate a Zn/Co substitution ability as assessed by growth rate. We investigated this diatom's inability to use Co to alleviate Zn‐limited growth rates at the transporter, sensor/chaperone, and metalloenzyme level using metal quota and proteomic analyses of cultures grown over a range of Zn and Co availability. Analysis of total cellular metal quotas revealed that, although incapable of substitution, this diatom still actively assimilated dissolved Co. We furthermore observed distinct trends in the abundance levels of putative α and θ‐CAs, ZIP transporters, Zn fingers, and a Zn chaperone in response to increasing media Zn 2+ . Overall, Co appears to be transported into the cell, but not efficiently utilized by Zn metalloenzymes.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Eruptive history of Mason Spur, a Miocene—Pleistocene polygenetic volcanic complex in southern Victoria Land, West Antarctic Rift System, Antarctica - John L. Smellie; Adam P. Martin; Gianfranco Di Vincenzo; Dougal B. Townsend; Matthew T. Heizler; Dawn C. S. Ruth (Bulletin of Volcanology, 2022)
Mason Spur is a deeply eroded Middle Miocene to Pleistocene (c. 13 to 0.37 Ma) volcanic complex in southern Victoria Land, within the West Antarctic Rift System (WARS). The oldest rocks include a large volume of trachyte ignimbrites that provided abundant volcanic detritus recovered in McMurdo Sound drill cores. The ignimbrites together with early-formed intrusions were strongly deformed during a substantial caldera collapse at c. 13 Ma. Intense erosion modified the volcanic landscape, creating a paleo-relief of several hundred metres. Deep ravines were cut and filled by deposits of multiple lahars probably linked to gravitational collapses of trachyte dome(s). Small-volume trachytic magmas were also erupted, forming lavas and at least one tuff cone. The youngest trachytic activity comprises a lava dome and related block-and-ash-flow deposits, erupted at 6 Ma. Basanite erupted throughout the history of the complex and eruptions younger than 12 Ma are almost exclusively basanite, forming scoria cones, water-cooled lavas, and tuff cones. Three peripheral outcrops are composed of basanitic ‘a‘ā lava-fed deltas, probably erupted from vents on neighbouring volcanoes at Mount Discovery and Mount Morning. Abundant ignimbrite deposits at Mason Spur differentiate this volcanic complex from others in the WARS. Eruptions were triggered by rift extension initially, yielding the voluminous trachytes sourced from a magma chamber on the margin of the WARS. Later mafic eruptions were associated with deep crustal faults related to residual intraplate deformation. These results add important details to the eruptive history of the intracontinental WARS.

Elevated inbreeding in Heliconia tortuosa is determined by tropical forest stand age, isolation and loss of hummingbird functional diversity - F. Andrew Jones; Adam S. Hadley; Kaitlin Bonner; Rakan A. Zahawi; W. Douglas Robinson; Urs Kormann; Matthew G. Betts (Molecular Ecology, 2022)
Forest conversion and habitat loss are major threats to biological diversity. Forest regeneration can mitigate the negative effects of old‐growth forest loss on species diversity, but less is known about the extent to which forest loss reduces genetic diversity in remnant populations and whether secondary forests play a role in the maintenance of genetic diversity. We quantified genetic diversity in a tropical hummingbird‐pollinated understorey herb, Heliconia tortuosa , across a landscape mosaic of primary and secondary forest regrowth. Using microsatellite genotypes from >850 adult and juvenile plants within 33 forest patches and extensive bird surveys, we examined the effect of contemporary and historical landscape features including forest age (primary vs. secondary forest), stand isolation and pollinator assemblages on genetic diversity and levels of inbreeding in H. tortuosa . We found that inbreeding was up to three times higher in secondary forest, and this effect was amplified with reductions in primary forest in the surrounding landscape through reduced observed heterozygosity in isolated fragments. Inbreeding in forest patches was negatively correlated with the local frequency of specialist long‐distance foraging traplining hummingbirds. Traplining hummingbirds therefore appear to facilitate mating among unrelated plants—an inference we tested using empirically parameterized simulations. Higher levels of inbreeding in H. tortuosa are therefore associated with reduced functional diversity of hummingbirds in secondary forests and forest patches isolated from primary forests. Our findings suggest a cryptic consequence of primary forest loss and secondary forest regeneration through the disruption of mutualistic interactions resulting in the erosion of genetic diversity in a common understorey plant.

Nutritional Considerations in High Performance Youth Soccer: A Systematic Review - Matthew North; Adam L. Kelly; Mayur K. Ranchordas; Matthew Cole (Journal of Science in Sport and Exercise, 2022)
Purpose As players in high performance youth soccer (HYPS) environments undergo large changes in growth and maturation throughout the course of their development, they require specific nutritional intakes if they are to meet these demands. The purpose of this review was to synthesise current nutritional research conducted within HYPS players. Methods A systematic approach, following PRISMA guidelines, was employed to capture all articles related to nutrition within HPYS using the databases MEDLINE and SPORTDiscus. Study quality and risk of bias were assessed using a Downs and Black instrument. Observational and intervention studies which investigated an element of nutritional status, knowledge, or intervention in academy aged players (U9 to U23s) within HPYS settings were included. Results Fifty-three articles qualified assessing: current nutritional intake and energy balance ( n = 21); ergogenic aids/supplements ( n = 13); hydration status ( n = 6); the influence of Ramadan fasting ( n = 4); Vitamin D status ( n = 4); female HPYS players ( n = 3); nutrition knowledge ( n = 2). Outcomes demonstrate a large proportion of HPYS players exhibit insufficient energy and carbohydrate intake, and a lack sufficient periodisation of nutrition to account for varying training/match loads. Large variability in energy intake and expenditure exists between and within chronological age groups, indicating the potential impact on growth and maturation. Female HPYS data is lacking but indicates similar trends to male counterparts. Conclusion HYPS players do not currently meet their energy requirements however the impact of growth and maturation is not fully understood. Furthermore, within this demographic future research is required into the barriers and enablers of players achieving adequate energy intake.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Interactive Effects of HIV Infection and Cannabis Use on Insula Subregion Functional Connectivity - Jessica S. Flannery; Michael C. Riedel; Taylor Salo; Lauren D. Hill-Bowen; Ranjita Poudel; Ashley R. Adams; Angela R. Laird; Raul Gonzalez; Matthew T. Sutherland (Journal of Neuroimmune Pharmacology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison of contrasting optical and LiDAR fire severity remote sensing methods in a heterogeneous forested landscape in south-eastern Australia - Matthew G. Gale; Geoffrey J. Cary; Marta Yebra; Adam J. Leavesley; Albert I. J. M. Van Dijk (International Journal of Remote Sensing, 2022)

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

Biotic factors limit the invasion of the plague pathogen ( Yersinia pestis ) in novel geographical settings - Henry G. Fell; Owen G. Osborne; Matthew D. Jones; Steve Atkinson; Simon Tarr; Suzanne H. Keddie; Adam C. Algar (Global Ecology and Biogeography, 2022)
Aim The distribution of Yersinia pestis , the pathogen that causes plague in humans, is reliant upon transmission between host species; however, the degree to which host species distributions dictate the distribution of Y. pestis , compared with limitations imposed by the environmental niche of Y. pestis per se, is debated. We test whether the present‐day environmental niche of Y. pestis differs between its native range and an invaded range and whether biotic factors (host distributions) can explain observed discrepancies. Location North America and Central Asia. Major taxa studied Yersinia pestis . Methods We use environmental niche models to determine whether the current climatic niche of Y. pestis differs between its native range in Asia and its invaded range in North America. We then test whether the inclusion of information on the distribution of host species improves the ability of models to capture the North American niche. We use geographical null models to guard against spurious correlations arising from spatially autocorrelated occurrence points. Results The current climatic niche of Y. pestis differs between its native and invaded regions. The Asian niche overpredicted the distribution of Y. pestis across North America. Including biotic factors along with the native climatic niche increased niche overlap between the native and invaded models, and models containing only biotic factors performed better than the native climatic niche alone. Geographical null models confirmed that the increased niche overlap through inclusion of biotic factors did not, with a couple of exceptions, arise solely from spatially autocorrelated occurrences. Main conclusions The current climatic niche in Central Asia differs from the current climatic niche in North America. Inclusion of biotic factors improved the fit of models to the Y. pestis distribution data in its invaded region better than climate variables alone. This highlights the importance of host species when investigating zoonotic disease introductions and suggests that climatic variables alone are insufficient to predict disease distribution in novel environments.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

How do fisher responses to macroalgal overgrowth influence the resilience of coral reefs? - Andrew Rassweiler; Scott D. Miller; Sally J. Holbrook; Matthew Lauer; Mark A. Strother; Sarah E. Lester; Thomas C. Adam; Jean Wencélius; Russell J. Schmitt (Limnology and Oceanography, 2022)
Many coral reefs have shifted from coral‐ to macroalgae‐dominated community states, heightening the need to understand resilience of coral communities. Fishing on herbivores often reduces resilience of the coral state, as lower herbivory fosters macroalgal establishment. Despite the acknowledged importance of fishing, relatively little attention has been paid to how fishers change their behavior as macroalgae overgrow reefs, or how the resulting dynamic feedbacks might affect resilience. We address these questions in Moorea, French Polynesia, where local fishers target herbivorous fishes and where shifts to algal dominance have occurred on some lagoon reefs. We quantified fisher preferences for reef habitats where they target various taxa. For the two most ecologically important taxa of herbivores targeted in the fishery, parrotfish (Scaridae) and unicornfish ( Naso ), fishers preferred to harvest from locations with less macroalgae. We incorporated these habitat preferences into a spatially explicit social–ecological model of reef dynamics to explore consequences of changes in fishing behavior for resilience of the coral state, particularly following disturbance. Fishing that targets low‐macroalgae locations typically generates resilience by facilitating local recovery of herbivores and thus of coral in the less‐targeted macroalgae‐dominated patches. However, the resulting movement of fishers across the seascape can sometimes create fragility; if coral loss is widespread, avoidance of macroalgae concentrates fishing in patches having the highest coral cover, resulting in loss of coral via reduced herbivory. Our results emphasize that resilience and coral‐macroalgae regime shifts cannot be understood without considering humans as a dynamic part of the system.

Complete genome of the thermophilic purple sulfur Bacterium Thermochromatium tepidum compared to Allochromatium vinosum and other Chromatiaceae - W. Matthew Sattley; Wesley D. Swingley; Brad M. Burchell; Emma D. Dewey; Mackenzie K. Hayward; Tara L. Renbarger; Kathryn N. Shaffer; Lynn M. Stokes; Sonja A. Gurbani; Catrina M. Kujawa; D. Adam Nuccio; Jacob Schladweiler; et al. (Photosynthesis Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Ocean warming threatens key trophic interactions supporting a commercial fishery in a climate change hotspot - Owen J. Holland; Mary A. Young; Craig D. H. Sherman; Mun Hua Tan; Harry Gorfine; Ty Matthews; Adam D. Miller (Global Change Biology, 2021)
Worldwide, rising ocean temperatures are causing declines and range shifts in marine species. The direct effects of climate change on the biology of marine organisms are often well documented; yet, knowledge on the indirect effects, particularly through trophic interactions, is largely lacking. We provide evidence of ocean warming decoupling critical trophic interactions supporting a commercially important mollusc in a climate change hotspot. Dietary assessments of the Australian blacklip abalone ( Haliotis rubra ) indicate primary dependency on a widespread macroalgal species ( Phyllospora comosa ) which we show to be in state of decline due to ocean warming, resulting in abalone biomass reductions. Niche models suggest further declines in P . comosa over the coming decades and ongoing risks to H . rubra . This study highlights the importance of studies from climate change hotspots and understanding the interplay between climate and trophic interactions when determining the likely response of marine species to environmental changes.

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Community Science for Coastal Acidification Monitoring and Research - Parker Randall Gassett; Katie O’Brien-Clayton; Carolina Bastidas; Jennie E. Rheuban; Christopher, W. Hunt; Elizabeth Turner; Matthew Liebman; Emily Silva; Adam, R. Pimenta; Jason. Grear; Jackie Motyka; Daniel McCorkle; et al. (Coastal Management, 2021)

Correction to: Field evaluation of seven products to control cyanobacterial blooms in aquaculture - Riley P. Buley; Catie Adams; Angelea P. Belfiore; Edna G. Fernandez-Figueroa; Matthew F. Gladfelter; Brynne Garner; David L. Straus; Alan E. Wilson (Environmental Science and Pollution Research, 2021)

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

The dimensionality and structure of species trait spaces - David Mouillot; Nicolas Loiseau; Matthias Grenié; Adam C. Algar; Michele Allegra; Marc W. Cadotte; Nicolas Casajus; Pierre Denelle; Maya Guéguen; Anthony Maire; Brian Maitner; Brian J. McGill; et al. (Ecology Letters, 2021)
Trait‐based ecology aims to understand the processes that generate the overarching diversity of organismal traits and their influence on ecosystem functioning. Achieving this goal requires simplifying this complexity in synthetic axes defining a trait space and to cluster species based on their traits while identifying those with unique combinations of traits. However, so far, we know little about the dimensionality, the robustness to trait omission and the structure of these trait spaces. Here, we propose a unified framework and a synthesis across 30 trait datasets representing a broad variety of taxa, ecosystems and spatial scales to show that a common trade‐off between trait space quality and operationality appears between three and six dimensions. The robustness to trait omission is generally low but highly variable among datasets. We also highlight invariant scaling relationships, whatever organismal complexity, between the number of clusters, the number of species in the dominant cluster and the number of unique species with total species richness. When species richness increases, the number of unique species saturates, whereas species tend to disproportionately pack in the richest cluster. Based on these results, we propose some rules of thumb to build species trait spaces and estimate subsequent functional diversity indices.

Effect of crossflow on trapping depths of particle plumes: laboratory experiments and application to the PLUMEX field experiment - Dayang Wang; E. Eric Adams; Carlos Munoz-Royo; Thomas Peacock; Matthew H. Alford (Environmental Fluid Mechanics, 2021)

RETRACTED: The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2021)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which multiple species share the same conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which vivid colour and pattern are produced in a Müllerian mimicry complex of poison frogs. We did this by first assembling a high‐quality de novo genome assembly for the mimic poison frog Ranitomeya imitator . This assembled genome is 6.8 Gbp in size, with a contig N50 of 300 Kbp R . imitator and two colour morphs from both Ranitomeya fantastica and R . variabilis which R . imitator mimics. We identified a large number of pigmentation and patterning genes that are differentially expressed throughout development, many of them related to melanocyte development, melanin synthesis, iridophore development and guanine synthesis. Polytypic differences within species may be the result of differences in expression and/or timing of expression, whereas convergence for colour pattern between species does not appear to be due to the same changes in gene expression. In addition, we identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species. Finally, we hypothesize that genes in the keratin family are important for producing different structural colours within these frogs.

Plant spectral diversity as a surrogate for species, functional and phylogenetic diversity across a hyper‐diverse biogeographic region - Henry A. Frye; Matthew E. Aiello‐Lammens; Douglas Euston‐Brown; Cynthia S. Jones; Hayley Kilroy Mollmann; Cory Merow; Jasper A. Slingsby; Helga van der Merwe; Adam M. Wilson; John A. Silander (Global Ecology and Biogeography, 2021)
Aim With plant biodiversity under global threat, there is an urgent need to monitor the spatial distribution of multiple axes of biodiversity. Remote sensing is a critical tool in this endeavour. One remote sensing approach for detecting biodiversity is based on the hypothesis that the spectral diversity of plant communities is a surrogate of multiple dimensions of biodiversity. We investigated the generality of this ‘surrogacy’ for spectral, species, functional and phylogenetic diversity across 1,267 plots in the Greater Cape Floristic Region (GCFR), a hyper‐diverse region comprising several biomes and two adjacent global biodiversity hotspots. Location The GCFR centred in south‐western and western South Africa. Time period All data were collected between 1978–2014. Major taxa studied Vascular plants within the GCFR. Methods Spectral diversity was calculated using leaf reflectance spectra (450–950 nm) and was related to other dimensions of biodiversity via linear models. The accuracy of different spectral diversity metrics was compared using 10‐fold cross‐validation. Results We found that a distance‐based spectral diversity metric was a robust predictor of species, functional and phylogenetic biodiversity. This result serves as a proof‐of‐concept that spectral diversity is a potential surrogate of biodiversity across a hyper‐diverse biogeographic region. While our results support the generality of spectral diversity as a biodiversity surrogate, we also find that relationships vary between different geographic subregions and biomes, suggesting that differences in broad‐scale community composition can affect these relationships. Main conclusions Spectral diversity was shown to be a robust surrogate of multiple dimensions of biodiversity across biomes and a widely varying biogeographic region. We also extend these surrogacy relationships to ecological redundancy to demonstrate the potential for additional insights into community structure based on spectral reflectance.

Important questions to progress science and sustainable management of anguillid eels - David Righton; Adam Piper; Kim Aarestrup; Elsa Amilhat; Claude Belpaire; John Casselman; Martin Castonguay; Estibaliz Díaz; Hendrik Dörner; Elisabeth Faliex; Eric Feunteun; Nobuto Fukuda; et al. (Fish and Fisheries, 2021)
Anguillid eels are found globally in fresh, transitional and saline waters and have played an important role in human life for centuries. The population status of several species is now of significant concern. The threats to populations include direct exploitation at different life stages, blockages to migratory routes by dams and other structures, changes in river basin management that impact habitat carrying capacity and suitability, pollution, climate change, diseases and parasites. While much has been done to understand eel biology and ecology, a major challenge is to identify the key research and management questions so that effective and targeted studies can be designed to inform conservation, management and policy. We gathered 30 experts in the field of eel biology and management to review the current state of knowledge for anguillid eel species and to identify the main topics for research. The identified research topics fell into three themes: (a) Lifecycle and Biology; (b) Impacts and (c) Management. Although tropical anguillid eels are by far the least well understood, significant knowledge gaps exist for all species. Considerable progress has been made in the last 20 years, but the status of many species remains of great concern, particularly for northern temperate species. Without improved engagement and coordination at the regional, national and international level, the situation is unlikely to improve. Further, adaptive management mechanisms to respond to developments in science, policy and our knowledge of potential threats are required to ensure the future of these important and enigmatic species.

Field evaluation of seven products to control cyanobacterial blooms in aquaculture - Riley P. Buley; Catie Adams; Angelea P. Belfiore; Edna G. Fernandez-Figueroa; Matthew F. Gladfelter; Brynne Garner; Alan E. Wilson (Environmental Science and Pollution Research, 2021)

Mangrove growth response to experimental warming is greatest near the range limit in northeast Florida - Samantha K. Chapman; Ilka C. Feller; Gabriela Canas; Matthew A. Hayes; Nicole Dix; Mark Hester; Jim Morris; J. Adam Langley (Ecology, 2021)
Shrubs are invading into grasslands around the world, but we don’t yet know how these shrubs will fare in a warmer future. In ecotonal coastal wetland ecosystems, woody mangroves are encroaching into herbaceous salt marshes owing to changes in temperature, precipitation, and sediment dynamics. Increasing mangrove biomass in wetlands often increases carbon storage, which is high in these productive ecosystems, but little is known about how mangrove growth will change in response to warming. To address this knowledge gap, we deployed warming experiments at three coastal wetland sites along a latitudinal gradient in northeast Florida where Avicennia germinans , black mangroves, are encroaching into salt marshes. We achieved air temperature warming (+1.6°C during the day) at all three sites and measured stem elongation, canopy height and area changes, and leaf and node number. After 2 yr of warming, we found that mangrove growth rate in height increased due to warming. Warming increased stem elongation by 130% over unwarmed control plots after 1 yr at the northern site. Mangrove growth in canopy area did not respond to warming. Site differences in growth rate were pronounced, and mangrove growth in both height and area were lowest at the northern site, despite greater impacts of warming at that site. We also found that area‐based relative growth rate was five times higher across all treatments than height‐based relative growth rate, indicating that mangroves are growing wider rather than taller in these ecotonal environments. Our findings indicate that the growth effect of experimental warming depends on site characteristics and growth parameter measured. We also propose that differential mangrove growth across the three sites may be driven by biotic factors such as the identity of the salt marsh species into which mangroves are encroaching. Our results suggest that, as seen in other ecosystems, wetland plants may respond most strongly to warming at their poleward range edge.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Element-Selective Targeting of Nutrient Metabolites in Environmental Samples by Inductively Coupled Plasma Mass Spectrometry and Electrospray Ionization Mass Spectrometry - Jingxuan Li; Rene M. Boiteau; Lydia Babcock-Adams; Marianne Acker; Zhongchang Song; Matthew R. McIlvin; Daniel J. Repeta (Frontiers in Marine Science, 2021)
Metabolites that incorporate elements other than carbon, nitrogen, hydrogen and oxygen can be selectively detected by inductively coupled mass spectrometry (ICPMS). When used in parallel with chromatographic separations and conventional electrospray ionization mass spectrometry (ESIMS), ICPMS allows the analyst to quickly find, characterize and identify target metabolites that carry nutrient elements (P, S, trace metals; “nutrient metabolites”), which are of particular interest to investigations of microbial biogeochemical cycles. This approach has been applied to the study of siderophores and other trace metal organic ligands in the ocean. The original method used mass search algorithms that relied on the ratio of stable isotopologues of iron, copper and nickel to assign mass spectra collected by ESIMS to metabolites carrying these elements detected by ICPMS. However, while isotopologue-based mass assignment algorithms were highly successful in characterizing metabolites that incorporate some trace metals, they do not realize the whole potential of the ICPMS/ESIMS approach as they cannot be used to assign the molecular ions of metabolites with monoisotopic elements or elements for which the ratio of stable isotopes is not known. Here we report a revised ICPMS/ESIMS method that incorporates a number of changes to the configuration of instrument hardware that improves sensitivity of the method by a factor of 4–5, and allows for more accurate quantitation of metabolites. We also describe a new suite of mass search algorithms that can find and characterize metabolites that carry monoisotopic elements. We used the new method to identify siderophores in a laboratory culture of Vibrio cyclitrophicus and a seawater sample collected in the North Pacific Ocean, and to assign molecular ions to monoisotopic cobalt and iodine nutrient metabolites in extracts of a laboratory culture of the marine cyanobacterium Prochorococcus MIT9215.

Elasmobranch Community Dynamics in Florida’s Southern Indian River Lagoon - Grace Roskar; Michael P. McCallister; Adam M. Schaefer; Matthew J. Ajemian (Estuaries and Coasts, 2021)

Invasion of an inconspicuous ambrosia beetle and fungus may affect wood decay in Southeastern North America - Jiri Hulcr; Demian F. Gomez; James Skelton; Andrew J. Johnson; Sawyer Adams; You Li; Michelle A. Jusino; Matthew E. Smith (Biological Invasions, 2021)

Grower Perceptions of Safety Hazards and Associated Injuries among Farmworkers Involved in Northwest Potato Production - Cynthia Curl; Karin Adams; Rachel Phinney; Matthew Blua (Journal of Agromedicine, 2021)

Dissimilatory nitrate reduction to ammonium increased with rising temperature - Thang V. Lai; Maarten H. Ryder; Judith R. Rathjen; Nanthi S. Bolan; Adam E. Croxford; Matthew D. Denton (Biology and Fertility of Soils, 2021)

Lava effusion rate evolution and erupted volume during the 2018 Kīlauea lower East Rift Zone eruption - Hannah R. Dietterich; Angela K. Diefenbach; S. Adam Soule; Michael H. Zoeller; Matthew P. Patrick; Jon J. Major; Paul R. Lundgren (Bulletin of Volcanology, 2021)

Social facilitation of alcohol subjective effects in adolescents: Associations with subsequent alcohol use - Matthew G. Kirkpatrick; Junhan Cho; Matthew D. Stone; Dayoung Bae; Jessica L. Barrington-Trimis; Raina D. Pang; Adam M. Leventhal (Psychopharmacology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Mesenchymal stem cell therapy in hypertrophic and keloid scars - Christine Bojanic; Kendrick To; Adam Hatoum; Jessie Shea; K. T. Matthew Seah; Wasim Khan; Charles M. Malata (Cell and Tissue Research, 2021)
Scars are the normal outcome of wound repair and involve a co-ordinated inflammatory and fibrotic process. When a scar does not resolve, uncontrolled chronic inflammation can persist and elicits excessive scarring that leads to a range of abnormal phenotypes such as hypertrophic and keloid scars. These pathologies result in significant impairment of quality of life over a long period of time. Existing treatment options are generally unsatisfactory, and there is mounting interest in innovative cell-based therapies. Despite the interest in mesenchymal stem cells (MSCs), there is yet to be a human clinical trial that investigates the potential of MSCs in treating abnormal scarring. A synthesis of existing evidence of animal studies may therefore provide insight into the barriers to human application. The aim of this PRISMA systematic review was to evaluate the effectiveness of MSC transplantation in the treatment of hypertrophic and keloid scars in in vivo models. A total of 11 case-control studies were identified that treated a total of 156 subjects with MSCs or MSC-conditioned media. Ten studies assessed hypertrophic scars, and one looked at keloid scars. All studies evaluated scars in terms of macroscopic and histological appearances and most incorporated immunohistochemistry. The included studies all found improvements in the above outcomes with MSC or MSC-conditioned media without complications. The studies reviewed support a role for MSC therapy in treating scars that needs further exploration. The transferability of these findings to humans is limited by factors such as the reliability and validity of the disease model, the need to identify the optimal MSC cell source, and the outcome measures employed.

Novel deep-water spawning patterns of bonefish (Albula vulpes), a shallow water fish - Steven M. Lombardo; Aaron J. Adams; Andy J. Danylchuk; Cameron A. Luck; Matthew J. Ajemian (Marine Biology, 2020)

Effects of Lespedeza cuneata invasion on tallgrass prairie plant and arthropod communities - Sofia Varriano; Krishna Patel; Luke Lefler; Carolina Kirksey; Adam Turner; Matthew D. Moran (Biological Invasions, 2020)

In situ recovery of bivalve shell characteristics after temporary exposure to elevated p CO 2 - Jason Grear; Adam Pimenta; Harriet Booth; Doranne Borsay Horowitz; Wilson Mendoza; Matthew Liebman (Limnology and Oceanography, 2020)
Ocean uptake of carbon dioxide (CO 2 ) is causing changes in carbonate chemistry that affects calcification in marine organisms. In coastal areas, this CO 2 ‐enriched seawater mixes with waters affected by seasonal degradation of organic material loaded externally from watersheds or produced as a response to nutrient enrichment. As a result, coastal bivalves often experience strong seasonal changes in carbonate chemistry. In some cases, these changes may resemble those experienced by aquacultured bivalves during translocation activities. We mimicked these changes by exposing juvenile hard clams (500 μ m, Mercenaria mercenaria ) to p CO 2 in laboratory upwellers at levels resembling those already reported for northeastern U.S. estuaries (mean upweller p CO 2 = 773, 1274, and 1838 μ atm) and then transplanting to three grow‐out sites along an expected nutrient gradient in Narragansett Bay, Rhode Island (154 bags of 100 clams). Prior to the field grow‐out, clams exposed to elevated p CO 2 exhibited larger shells but lower dry weight per unit volume (dw/V). However, percent increase in dw/V was highest for this group during the 27‐day field grow‐out, suggesting that individuals with low dw/V after the laboratory treatment accelerated accumulation of dw/V when they were transferred to the bay. Treatments also appeared to affect shell mineral structure and condition of digestive diverticula. Although treatment effects diminished during the field grow‐out, clams that were preexposed for several weeks to high p CO 2 would likely have been temporarily vulnerable to predation or other factors that interact with shell integrity. This would be expected to reduce population recovery from short‐term exposures to high p CO 2 .

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

Design and Evaluation of a Multiplexed Assay to Assess Human Immunogenicity Against Humira® - Matthew Alleyn; Kristin Closson; Adam Gentile; Nathan Gulbis; Christopher Taylor; Paul Rhyne (The AAPS Journal, 2020)
The use of biologic-based therapeutics has revolutionized our ability to treat complex diseases such as cancer- and autoimmune-related disorders. Biologic-based therapeutics are known to generate anti-drug immune responses or immunogenicity in clinical patients which can lead to altered pharmacokinetics, decreased drug efficacy, and unwanted adverse clinical events. Assays designed to detect and assess anti-drug immune responses are used to help monitor patients and improve drug safety. Utilizing a tiered approach, screening assays are developed first to identify patients that are potentially positive for anti-drug-specific antibodies. Patients that screen positive are subjected to additional tiers of testing that include a confirmation assay to confirm the presence of expected anti-drug-specific antibodies, a titer assay to assess relative levels of anti-drug-specific antibodies, and, depending on the drug’s mechanism of action or concerns of adverse clinical reactions, further characterization such as drug neutralization and anti-drug antibody isotyping. This tiered approach can prove to be detrimental to clinical samples from exposure to multiple cycles of testing, freeze thaws, and repeated handling by lab personnel. Multiplexing some of these assays together may streamline the characterization of anti-drug immune responses and help reduce the repeated usage of clinical samples. In this study, we combined a screening assay and anti-drug isotyping assays into one multiplexed assay using the Luminex® xMAP® Technology. The multiplexed assay was developed and validated to meet the FDA recommended guidelines for immunogenicity assessments. These results show that multiplexed assays perform comparably to industry standards. This study should encourage labs to explore the use of multiplexing immunogenicity assays to characterize anti-drug antibody responses quickly, with less repeat testing and reduced sample handling.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Plio‐Pleistocene sea‐level changes drive speciation of freshwater fishes in north‐western Australia - James J. Shelley; Stephen E. Swearer; Tim Dempster; Mark Adams; Matthew C. Le Feuvre; Michael P. Hammer; Peter J. Unmack (Journal of Biogeography, 2020)
Aim Despite the influence of sea‐level changes on biogeographic/phylogeographic patterns in freshwater ecosystems being well documented, studies that explicitly link the influence of sea‐level change with speciation are rare. We aim to test the hypothesis that sea‐level changes during the Pliocene and Pleistocene have driven speciation in north‐western Australia's (NWA’s) largest freshwater fish family, Terapontidae, building upon a body of evolutionary literature focussed on the family. Location North‐western Australian rivers including those draining the Kimberley Plateau. Taxon Grunters (Family: Terapontidae, Genera: Hannia , Hephaestus , Leiopotherapon , Syncomistes ). Methods A GIS was used to reconstruct palaeodrainages during lowered sea levels and to delineate regions of high connectivity during low and high (current) sea‐level conditions. For seven species, the degree of phylogenetic divergence among river basins in different regions was evaluated using a maximum likelihood phylogeny and analyses of the proportion of genetic divergence expressed with 601 base pairs of the mtDNA cytochrome b (cytb) gene. Results A low proportion of cytb haplotypes were shared among catchments not connected by the same receiving waters (e.g. estuaries) under current (high) sea levels, indicating that contemporary dispersal is limited over fine spatial scales. Deeper phylogeographic patterns were largely congruent with reconstructed low sea‐level (LSL) drainage arrangements indicating that historic among‐catchment connectivity was far more widespread under LSL conditions. Main Conclusions The NWA landscape represents a geographic template that has shaped patterns of broad dispersal under low sea levels, and fine‐scale isolation under high sea levels. The weight of evidence from recent literature on species boundaries and evolutionary patterns within the terapontids suggests that most NWA species were derived rapidly and recently from a series of spatio‐temporal vicariant events caused by such sea‐level fluctuations during the late Pliocene and Pleistocene. Together, the findings provide a rare, comprehensively tested example of sea‐level change driving speciation in the tropics.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

The curious case of bunnies: interpretation of the lagomorph index from Homol’ovi I, Room 733 - Kassi S. Bailey; Matthew J. Rowe; E. Charles Adams (Archaeological and Anthropological Sciences, 2020)

Multi-dimensional well-being associated with economic dependence on ecosystem services in deltaic social-ecological systems of Bangladesh - Helen Adams; W. Neil Adger; Sate Ahmad; Ali Ahmed; Dilruba Begum; Zoe Matthews; Mohammed Mofizur Rahman; Kristine Nilsen; Georgina Grace Gurney; Peter Kim Streatfield (Regional Environmental Change, 2020)
While the benefits humans gain from ecosystem functions and processes are critical in natural resource-dependent societies with persistent poverty, ecosystem services as a pathway out of poverty remain an elusive goal, contingent on the ecosystem and mediated by social processes. Here, we investigate three emerging dimensions of the ecosystem service-poverty relationship: economic contribution of provisioning ecosystem services to the household livelihood mix, social-ecological systems producing different bundles of ecosystem services and material wealth versus reported life satisfaction. We analyse these relationships in Bangladesh, using data from a bespoke 1586-household survey, stratified by seven social-ecological systems in the delta coastal region. We create poverty lines to ensure comparability with traditional poverty measures that overlook environmental factors and subjective measurements of well-being. We find that any contribution of ecosystem service-based income to the livelihood mix decreases the likelihood of the incidence of poverty, and of individuals reporting dissatisfaction. We find no relationship between the incidence of material poverty and the specific social-ecological systems, from agriculture to fishery-dominated systems. However, the probability of the household head being dissatisfied was significantly associated with social-ecological system. Individuals living in areas dominated by export-oriented shrimp aquaculture reported lower levels of life satisfaction as an element of their perceived well-being. These results highlight the need for social policy on poverty that accounts for the diversity of outcomes across social-ecological systems, including subjective as well as material dimensions of well-being. National poverty reduction that degrades ecosystem services can have negative implications for the subjective well-being of local populations.

Effectiveness of transdermal nicotine patch in premenopausal female smokers is moderated by within-subject severity of negative affect and physical symptoms - Stephanie H. Chai; Adam M. Leventhal; Matthew G. Kirkpatrick; Tory A. Eisenlohr-Moul; Andrea J. Rapkin; Lina D’Orazio; Raina D. Pang (Psychopharmacology, 2020)

Dual-sectored transurethral ultrasound for thermal treatment of stress urinary incontinence: in silico studies in 3D anatomical models - Dong Liu; Matthew Adams; E. Clif Burdette; Chris J. Diederich (Medical & Biological Engineering & Computing, 2020)

A novel tissue culture model for evaluating the effect of aging on stem cell fate in adult microvascular networks - Mohammad S. Azimi; Jessica M. Motherwell; Maria Dutreil; Ryan L. Fishel; Matthew Nice; Nicholas A. Hodges; Bruce A. Bunnell; Adam Katz; Walter L. Murfee (GeroScience, 2020)

Reproductive physiology of bonefishes (Albula spp.) across the Northwest Bahamas - Sahar Mejri; Cameron Luck; Paul S. Wills; Aaron Adams; Jonathan Shenker; Matthew J. Ajemian (Fish Physiology and Biochemistry, 2020)

Informing management decisions for ecological networks, using dynamic models calibrated to noisy time‐series data - Matthew P. Adams; Scott A. Sisson; Kate J. Helmstedt; Christopher M. Baker; Matthew H. Holden; Michaela Plein; Jacinta Holloway; Kerrie L. Mengersen; Eve McDonald‐Madden (Ecology Letters, 2020)
Well‐intentioned environmental management can backfire, causing unforeseen damage. To avoid this, managers and ecologists seek accurate predictions of the ecosystem‐wide impacts of interventions, given small and imprecise datasets, which is an incredibly difficult task. We generated and analysed thousands of ecosystem population time series to investigate whether fitted models can aid decision‐makers to select interventions. Using these time‐series data (sparse and noisy datasets drawn from deterministic Lotka‐Volterra systems with two to nine species, of known network structure), dynamic model forecasts of whether a species’ future population will be positively or negatively affected by rapid eradication of another species were correct > 70% of the time. Although 70% correct classifications is only slightly better than an uninformative prediction (50%), this classification accuracy can be feasibly improved by increasing monitoring accuracy and frequency. Our findings suggest that models may not need to produce well‐constrained predictions before they can inform decisions that improve environmental outcomes.

Life cycle assessment of emerging technologies: Evaluation techniques at different stages of market and technical maturity - Joule A. Bergerson; Adam Brandt; Joe Cresko; Michael Carbajales‐Dale; Heather L. MacLean; H. Scott Matthews; Sean McCoy; Marcelle McManus; Shelie A. Miller; William R. Morrow; I. Daniel Posen; Thomas Seager; et al. (Journal of Industrial Ecology, 2020)
Life cycle assessment (LCA) analysts are increasingly being asked to conduct life cycle‐based systems level analysis at the earliest stages of technology development. While early assessments provide the greatest opportunity to influence design and ultimately environmental performance, it is the stage with the least available data, greatest uncertainty, and a paucity of analytic tools for addressing these challenges. While the fundamental approach to conducting an LCA of emerging technologies is akin to that of LCA of existing technologies, emerging technologies pose additional challenges. In this paper, we present a broad set of market and technology characteristics that typically influence an LCA of emerging technologies and identify questions that researchers must address to account for the most important aspects of the systems they are studying. The paper presents: (a) guidance to identify the specific technology characteristics and dynamic market context that are most relevant and unique to a particular study, (b) an overview of the challenges faced by early stage assessments that are unique because of these conditions, (c) questions that researchers should ask themselves for such a study to be conducted, and (d) illustrative examples from the transportation sector to demonstrate the factors to consider when conducting LCAs of emerging technologies. The paper is intended to be used as an organizing platform to synthesize existing methods, procedures and insights and guide researchers, analysts and technology developer to better recognize key study design elements and to manage expectations of study outcomes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Exploring rain forest diversification using demographic model testing in the African foam‐nest treefrog Chiromantis rufescens - Adam D. Leaché; Daniel M. Portik; Danielle Rivera; Mark‐Oliver Rödel; Johannes Penner; Václav Gvoždík; Eli Greenbaum; Gregory F. M. Jongsma; Caleb Ofori‐Boateng; Marius Burger; Edem A. Eniang; Rayna C. Bell; et al. (Journal of Biogeography, 2019)
Aim Species with wide distributions spanning the African Guinean and Congolian rain forests are often composed of genetically distinct populations or cryptic species with geographic distributions that mirror the locations of the remaining forest habitats. We used phylogeographic inference and demographic model testing to evaluate diversification models in a widespread rain forest species, the African foam‐nest treefrog Chiromantis rufescens . Location Guinean and Congolian rain forests, West and Central Africa. Taxon Chiromantis rufescens . Methods We collected mitochondrial DNA (mtDNA) and single‐nucleotide polymorphism (SNP) data for 130 samples of C. rufescens . After estimating population structure and inferring species trees using coalescent methods, we tested demographic models to evaluate alternative population divergence histories that varied with respect to gene flow, population size change and periods of isolation and secondary contact. Species distribution models were used to identify the regions of climatic stability that could have served as forest refugia since the last interglacial. Results Population structure within C. rufescens resembles the major biogeographic regions of the Guinean and Congolian forests. Coalescent‐based phylogenetic analyses provide strong support for an early divergence between the western Upper Guinean forest and the remaining populations. Demographic inferences support diversification models with gene flow and population size changes even in cases where contemporary populations are currently allopatric, which provides support for forest refugia and barrier models. Species distribution models suggest that forest refugia were available for each of the populations throughout the Pleistocene. Main conclusions Considering historical demography is essential for understanding population diversification, especially in complex landscapes such as those found in the Guineo–Congolian forest. Population demographic inferences help connect the patterns of genetic variation to diversification model predictions. The diversification history of C. rufescens was shaped by a variety of processes, including vicariance from river barriers, forest fragmentation and adaptive evolution along environmental gradients.

Editorial: Canopies in Aquatic Ecosystems: Integrating Form, Function, and Biophysical Processes - Julia E. Samson; Marco Ghisalberti; Matthew Philip Adams; Matthew A. Reidenbach; Matthew H. Long; Uri Shavit; Virginia B. Pasour (Frontiers in Marine Science, 2019)

Intramuscular fast-flow vascular anomaly contains somatic MAP2K1 and KRAS mutations - Jeremy A. Goss; Dennis J. Konczyk; Patrick J. Smits; Harry P. W. Kozakewich; Ahmad I. Alomari; Alyaa Al-Ibraheemi; Amir H. Taghinia; Belinda H. Dickie; Denise M. Adams; Steven J. Fishman; John B. Mulliken; Matthew L. Warman; et al. (Angiogenesis, 2019)

Significance of non-stationary characteristics of ground-motion on structural damage: shaking table study - Mohammad M. Kashani; Xiao Ge; Matthew S. Dietz; Adam J. Crewe; Nicholas A. Alexander (Bulletin of Earthquake Engineering, 2019)

Investigation and modeling of direct toppling using a three-dimensional distinct element approach with incorporation of point cloud geometry - Claudio Vanneschi; Matthew Eyre; Adam Venn; John S. Coggan (Landslides, 2019)

Population genetics, speciation, and hybridization in Dicerandra (Lamiaceae), a North American Coastal Plain endemic, and implications for conservation - Adam C. Payton; Andre A. Naranjo; Walter Judd; Matthew Gitzendanner; Pamela S. Soltis; Douglas E. Soltis (Conservation Genetics, 2019)

Cellular energetics and mitochondrial uncoupling in canine aging - Justin W. Nicholatos; Timothy M. Robinette; Saurabh V.P. Tata; Jennifer D. Yordy; Adam B. Francisco; Michael Platov; Tiffany K. Yeh; Olga R. Ilkayeva; Frank K. Huynh; Maxim Dokukin; Dmytro Volkov; Michael A. Weinstein; et al. (GeroScience, 2019)

A computational fluid dynamics (CFD) based method for assessing the hydrodynamic impact of animal borne data loggers on host marine mammals - Adam Kyte; Christopher Pass; Richard Pemberton; Matthew Sharman; J. Chris McKnight (Marine Mammal Science, 2019)
Animal‐borne data loggers (ABDLs) or “tags” are regularly used to elucidate animal ecology and physiology, but current literature highlights the need to assess associated deleterious impacts including increased resistive force to motion. Previous studies have used computational fluid dynamics (CFD) to estimate this impact, but many suffer limitations ( e.g ., inaccurate turbulence modeling, neglecting boundary layer transition, neglecting added mass effects, and analyzing the ABDL in isolation from the animal). A novel CFD‐based method is presented in which a “tag impact envelope” is defined utilizing simulations with and without transition modeling to define upper and lower drag limits, respectively, and added mass coefficients are found via simulations with sinusoidally varying inlet velocity, with modified Navier‐Stokes conservation of momentum equations enforcing a shift to the animal's noninertial reference frame. The method generates coefficients for calculating total resistive force for any velocity and acceleration combination, and is validated against theory for a prolate spheroid. An example case shows ABDL drag impact on a harp seal of 11.21%–16.24%, with negligible influence on added mass. By considering the effects of added mass and boundary layer transition, the approach presented is an enhancement to the CFD‐based ABDL impact assessment methods previously applied by researchers.

Local adaptation, genetic divergence, and experimental selection in a foundation grass across the US Great Plains’ climate gradient - Matthew Galliart; Nora Bello; Mary Knapp; Jesse Poland; Paul St Amand; Sara Baer; Brian Maricle; Adam B. Smith; Loretta Johnson (Global Change Biology, 2019)
Many prior studies have uncovered evidence for local adaptation using reciprocal transplant experiments. However, these studies are rarely conducted for a long enough time to observe succession and competitive dynamics in a community context, limiting inferences for long‐lived species. Furthermore, the genetic basis of local adaptation and genetic associations with climate has rarely been identified. Here, we report on a long‐term (6‐year) experiment conducted under natural conditions focused on Andropogon gerardii, the dominant grass of the North American Great Plains tallgrass ecosystem. We focus on this foundation grass that comprises 80% of tallgrass prairie biomass and is widely used in 20,000 km 2 of restoration. Specifically, we asked the following questions: (a) Whether ecotypes are locally adapted to regional climate in realistic ecological communities. (b) Does adaptive genetic variation underpin divergent phenotypes across the climate gradient? (c) Is there evidence of local adaptation if the plants are exposed to competition among ecotypes in mixed ecotype plots? Finally, (d) are local adaptation and genetic divergence related to climate? Reciprocal gardens were planted with 3 regional ecotypes (originating from dry, mesic, wet climate sources) of Andropogon gerardii across a precipitation gradient (500–1,200 mm/year) in the US Great Plains. We demonstrate local adaptation and differentiation of ecotypes in wet and dry environments. Surprisingly, the apparent generalist mesic ecotype performed comparably under all rainfall conditions. Ecotype performance was underpinned by differences in neutral diversity and candidate genes corroborating strong differences among ecotypes. Ecotype differentiation was related to climate, primarily rainfall. Without long‐term studies, wrong conclusions would have been reached based on the first two years. Further, restoring prairies with climate‐matched ecotypes is critical to future ecology, conservation, and sustainability under climate change.

Seasonal and spatial changes in sex hormone levels and oocyte development of bonefish (Albula vulpes) - Cameron Luck; Sahar Mejri; Justin Lewis; Paul S. Wills; Marty Riche; Jonathan Shenker; Aaron Adams; Matthew J. Ajemian (Environmental Biology of Fishes, 2019)

Bonefish (Albula vulpes) oocyte lipid class and fatty acid composition related to their development - Sahar Mejri; Cameron Luck; Rejean Tremblay; Marty Riche; Aaron Adams; Matthew J. Ajemian; Jonathan Shenker; Paul S. Wills (Environmental Biology of Fishes, 2019)

Interaction between invasive plant leaf litter and NaCl on two model amphibians - Devin G. DiGiacopo; George A. Meindl; Sean Ryan; Jared Jaeger; Matthew Wersebe; Amelia Martin; Seth A. Robinson; Gabrielle Graham; Adam R. Palmer; Amanda Setteducate; Ian Murray; Kirsten Prior; et al. (Biological Invasions, 2019)

A Web-Based Atlas Combining MRI and Histology of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Matthew Christian; Vaibhav Janve; Iwona Stepniewska; Bennett A. Landman; Adam W. Anderson (Neuroinformatics, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Genomewide SNP markers breathe new life into phylogeography and species delimitation for the problematic short‐necked turtles (Chelidae: Emydura ) of eastern Australia - Arthur Georges; Bernd Gruber; Greg B. Pauly; Duanne White; Mark Adams; Matthew J. Young; Andrzej Kilian; Xiuwen Zhang; H. Bradley Shaffer; Peter J. Unmack (Molecular Ecology, 2018)
Understanding the evolutionary history of diversifying lineages and the delineation of evolutionarily significant units and species remains major challenges for evolutionary biology. Low‐cost representational sampling of the genome for single nucleotide polymorphisms shows great potential at the temporal scales that are typically the focus of species delimitation and phylogeography. We apply these markers to a case study of a freshwater turtle, Emydura macquarii , whose systematics has so far defied resolution, to bring to light a dynamic system of substantive allopatric lineages diverging on independent evolutionary trajectories, but held back in the process of speciation by low level and episodic exchange of alleles across drainage divides on various timescales. In the context of low‐level episodic gene flow, speciation is often reticulate, rather than a bifurcating process. We argue that species delimitation needs to take into account the pattern of ancestry and descent of diverging lineages in allopatry together with the recent and contemporary processes of dispersal and gene flow that retard and obscure that divergence. Underpinned by a strong focus on lineage diagnosability, this combined approach provides a means for addressing the challenges of incompletely isolated populations with uncommon, but recurrent gene flow in studies of species delimitation, a situation likely to be frequently encountered. Taxonomic decisions in cases of allopatry often require subjective judgements. Our strategy, which adds an additional level of objectivity before that subjectivity is applied, reduces the risk of taxonomic inflation that can accompany lineage approaches to species delimitation.

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Sky, sea, and forest islands: Diversification in the African leaf‐folding frog Afrixalus paradorsalis (Anura: Hyperoliidae) of the Lower Guineo‐Congolian rain forest - Kristin L. Charles; Rayna C. Bell; David C. Blackburn; Marius Burger; Matthew K. Fujita; Václav Gvoždík; Gregory F.M. Jongsma; Marcel Talla Kouete; Adam D. Leaché; Daniel M. Portik (Journal of Biogeography, 2018)
Aim To investigate how putative barriers, forest refugia, and ecological gradients across the lower Guineo‐Congolian rain forest shape genetic and phenotypic divergence in the leaf‐folding frog Afrixalus paradorsalis , and examine the role of adjacent land bridge and sky‐islands in diversification. Location The Lower Guineo‐Congolian Forest, the Cameroonian Volcanic Line (CVL), and Bioko Island, Central Africa. Taxon Afrixalus paradorsalis (Family: Hyperoliidae), an African leaf‐folding frog. Methods We used molecular and phenotypic data to investigate diversity and divergence among the A. paradorsalis species complex distributed across lowland rain forests, a land bridge island, and mountains in Central Africa. We examined the coincidence of population boundaries, landscape features, divergence times, and spatial patterns of connectivity and diversity, and subsequently performed demographic modelling using genome‐wide SNP variation to distinguish among divergence mechanisms in mainland (riverine barriers, forest refugia, ecological gradients) and land bridge island populations (vicariance, overwater dispersal). Results We detected four genetically distinct allopatric populations corresponding to Bioko Island, the CVL, and two lowland rain forest populations split by the Sanaga River. Although lowland populations are phenotypically indistinguishable, pronounced body size evolution occurs at high elevation, and the timing of the formation of the high elevation population coincides with mountain uplift in the CVL. Spatial analyses and demographic modelling revealed population divergence across mainland Lower Guinea is best explained by forest refugia rather than riverine barriers or ecological gradients, and that the Bioko Island population divergence is best explained by vicariance (marine incursion) rather than overseas dispersal. Main conclusions We provide growing support for the important role of forest refugia in driving intraspecific divergences in the Guineo‐Congolian rain forest. In A. paradorsalis , sky‐islands in the CVL have resulted in greater genetic and phenotypic divergences than marine incursions of the land bridge Bioko Island, highlighting important differences in patterns of island‐driven diversification in Lower Guinea.

A genomic evaluation of taxonomic trends through time in coast horned lizards (genus Phrynosoma ) - Adam D. Leaché; Matthew T. McElroy; Anna Trinh (Molecular Ecology, 2018)
Determining the boundaries between species and deciding when to describe new species are challenging practices that are particularly difficult in groups with high levels of geographic variation. The coast horned lizards ( Phrynosoma blainvillii , Phrynosoma cerroense and P. coronatum ) have an extensive geographic distribution spanning many distinctive ecological regions ranging from northern California to the Cape Region of Baja California, Mexico, and populations differ substantially with respect to external morphology across much of this range. The number of taxa recognized in the group has been reevaluated by herpetologists over 20 times during the last 180 years, and typically without the aid of explicit species delimitation methods, resulting in a turbulent taxonomy containing anywhere from one to seven taxa. In this study, we evaluate taxonomic trends through time by ranking 15 of these species delimitation models ( SDM s) using coalescent analyses of nuclear loci and SNP s in a Bayesian model comparison framework. Species delimitation models containing more species were generally favoured by Bayesian model selection; however, several three‐species models outperformed some four‐ and five‐species SDM s, and the top‐ranked model, which contained five species, outperformed all SDM s containing six species. Model performance peaked in the 1950s based on marginal likelihoods estimated from nuclear loci and SNP s. Not surprisingly, SDM s based on genetic data outperformed morphological taxonomies when using genetic data alone to evaluate models. The de novo estimation of population structure favours a three‐population model that matches the currently recognized integrative taxonomy containing three species. We discuss why Bayesian model selection might favour models containing more species, and why recognizing more than three species might be warranted.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Illuminating the link between perceived threat and control over climate change: the role of attributions for causation and mitigation - Julie Davydova; Adam R. Pearson; Matthew T. Ballew; Jonathon P. Schuldt (Climatic Change, 2018)

The “jack‐in‐the‐box” stamens of Heliconia wagneriana (Heliconiaceae) - Dustin G. Gannon; Urs G. Kormann; Adam S. Hadley; Matthew G. Betts; Franklin Andrew Jones (Ecology, 2018)

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Sedentary time and postmenopausal breast cancer incidence - Sarah J. O. Nomura; Chiranjeev Dash; Vanessa B. Sheppard; Deborah Bowen; Matthew Allison; Wendy Barrington; Rowan Chlebowski; Mace Coday; Lifang Hou; Barbara Howard; Michael LaMonte; JoAnn E. Manson; et al. (Cancer Causes & Control, 2017)

Particulate matter intake fractions for vehicular emissions at elementary schools in Hamilton, Canada: an assessment of outdoor and indoor exposure - Weeberb J. Requia; Matthew D. Adams; Altaf Arain; Mark Ferguson (Air Quality, Atmosphere & Health, 2017)

Evaluating mechanisms of diversification in a Guineo‐Congolian tropical forest frog using demographic model selection - Daniel M. Portik; Adam D. Leaché; Danielle Rivera; Michael F. Barej; Marius Burger; Mareike Hirschfeld; Mark‐Oliver Rödel; David C. Blackburn; Matthew K. Fujita (Molecular Ecology, 2017)
The accumulation of biodiversity in tropical forests can occur through multiple allopatric and parapatric models of diversification, including forest refugia, riverine barriers and ecological gradients. Considerable debate surrounds the major diversification process, particularly in the West African Lower Guinea forests, which contain a complex geographic arrangement of topographic features and historical refugia. We used genomic data to investigate alternative mechanisms of diversification in the Gaboon forest frog, Scotobleps gabonicus , by first identifying population structure and then performing demographic model selection and spatially explicit analyses. We found that a majority of population divergences are best explained by allopatric models consistent with the forest refugia hypothesis and involve divergence in isolation with subsequent expansion and gene flow. These population divergences occurred simultaneously and conform to predictions based on climatically stable regions inferred through ecological niche modelling. Although forest refugia played a prominent role in the intraspecific diversification of S. gabonicus , we also find evidence for potential interactions between landscape features and historical refugia, including major rivers and elevational barriers such as the Cameroonian Volcanic Line. We outline the advantages of using genomewide variation in a model‐testing framework to distinguish between alternative allopatric hypotheses, and the pitfalls of limited geographic and molecular sampling. Although phylogeographic patterns are often species‐specific and related to life‐history traits, additional comparative studies incorporating genomic data are necessary for separating shared historical processes from idiosyncratic responses to environmental, climatic and geological influences on diversification.

Decoupled responses of soil bacteria and their invertebrate consumer to warming, but not freeze–thaw cycles, in the Antarctic Dry Valleys - Matthew A. Knox; Walter S. Andriuzzi; Heather N. Buelow; Cristina Takacs‐Vesbach; Byron J. Adams; Diana H. Wall (Ecology Letters, 2017)
Altered temperature profiles resulting in increased warming and freeze–thaw cycle ( FTC ) frequency pose great ecological challenges to organisms in alpine and polar ecosystems. We performed a laboratory microcosm experiment to investigate how temperature variability affects soil bacterial cell numbers, and abundance and traits of soil microfauna (the microbivorous nematode Scottnema lindsayae ) from McMurdo Dry Valleys, Antarctica. FTC s and constant freezing shifted nematode body size distribution towards large individuals, driven by higher mortality among smaller individuals. FTC s reduced both bacterial and nematode abundance, but bacterial cell numbers also declined under warming, demonstrating decoupled consumer–prey responses. We predict that higher occurrence of FTC s in cold ecosystems will select for large body size within soil microinvertebrates and overall reduce their abundance. In contrast, warm temperatures without FTC s could lead to divergent responses in soil bacteria and their microinvertebrate consumers, potentially affecting energy and nutrient transfer rates in soil food webs of cold ecosystems.

Complete sequence and genomic annotation of carrot torradovirus 1 - Zuriñe Rozado-Aguirre; Ian Adams; Adrian Fox; Matthew Dickinson; Neil Boonham (Archives of Virology, 2017)

Bayesian inference of species diffusion in the West African Agama agama species group (Reptilia, Agamidae) - Adam D. Leaché; Jared A. Grummer; Michael Miller; Sneha Krishnan; Matthew K. Fujita; Wolfgang Böhme; Andreas Schmitz; Matthew Lebreton; Ivan Ineich; Laurent Chirio; Caleb Ofori-boateng; Edem A. Eniang; et al. (Systematics and Biodiversity, 2017)

Sexual dimorphism in obesity-related genes in the epicardial fat during aging - Caitlin Kocher; Matthew Christiansen; Sarah Martin; Christopher Adams; Paulette Wehner; Todd Gress; Nalini Santanam (Journal of Physiology and Biochemistry, 2017)

Persistent Organic Pollutant and Hormone Levels in Harbor Porpoise with B Cell Lymphoma - Stephanie A. Norman; Zach C. Winfield; Barry H. Rickman; Sascha Usenko; Matthew Klope; Susan Berta; Sandra Dubpernell; Howard Garrett; Mary Jo Adams; Dyanna Lambourn; Jessica L. Huggins; Nadine Lysiak; et al. (Archives of Environmental Contamination and Toxicology, 2017)

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Pharmacogenetics of stimulant abuse liability: association of CDH13 variant with amphetamine response in a racially-heterogeneous sample of healthy young adults - Adam M. Leventhal; Matthew G. Kirkpatrick; Mollie S. Pester; John E. McGeary; Robert M. Swift; Steve Sussman; Christopher W. Kahler (Psychopharmacology, 2017)

Evidence for sex-specific reproductive senescence in monogamous cooperatively breeding red wolves - Amanda M. Sparkman; Matthew Blois; Jennifer Adams; Lisette Waits; David A.W. Miller; Dennis L. Murray (Behavioral Ecology and Sociobiology, 2017)

Behavioral evidence suggests facultative scavenging by a marine apex predator during a food pulse - Neil Hammerschlag; Ian Bell; Richard Fitzpatrick; Austin J. Gallagher; Lucy A. Hawkes; Mark G. Meekan; John D. Stevens; Michele Thums; Matthew J. Witt; Adam Barnett (Behavioral Ecology and Sociobiology, 2016)

Tests of ecogeographical relationships in a non-native species: what rules avian morphology? - Adam P. A. Cardilini; Katherine L. Buchanan; Craig D. H. Sherman; Phillip Cassey; Matthew R. E. Symonds (Oecologia, 2016)

Refocusing Habitat Fragmentation Research Using Lessons from the Last Decade - Adam S. Hadley; Matthew G. Betts (Current Landscape Ecology Reports, 2016)

Shifting targets: spatial priorities for ex situ plant conservation depend on interactions between current threats, climate change, and uncertainty - Adam B. Smith; Quinn G. Long; Matthew A. Albrecht (Biodiversity and Conservation, 2016)

Impact of diurnal freeze–thaw cycles on the soil nematode Scottnema lindsayae in Taylor Valley, Antarctica - Matthew A. Knox; Diana H. Wall; Ross A. Virginia; Martijn L. Vandegehuchte; Inigo San Gil; Byron J. Adams (Polar Biology, 2016)

Adaptive governance to promote ecosystem services in urban green spaces - Olivia Odom Green; Ahjond S. Garmestani; Sandra Albro; Natalie C. Ban; Adam Berland; Caitlin E. Burkman; Mary M. Gardiner; Lance Gunderson; Matthew E. Hopton; Michael L. Schoon; William D. Shuster (Urban Ecosystems, 2016)

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

Light history-dependent respiration explains the hysteresis in the daily ecosystem metabolism of seagrass - Matthew P. Adams; Angus J. P. Ferguson; Paul S. Maxwell; Brodie A. J. Lawson; Jimena Samper-Villarreal; Katherine R. O’Brien (Hydrobiologia, 2016)

Emotional traits predict individual differences in amphetamine-induced positive mood in healthy volunteers - Matthew G. Kirkpatrick; Nicholas I. Goldenson; Nahel Kapadia; Christopher W. Kahler; Harriet de Wit; Robert M. Swift; John E. McGeary; Steve Sussman; Adam M. Leventhal (Psychopharmacology, 2016)

What do metabolic rates tell us about thermal niches? Mechanisms driving crayfish distributions along an altitudinal gradient - Rick J. Stoffels; Adam J. Richardson; Matthew T. Vogel; Simon P. Coates; Warren J. Müller (Oecologia, 2016)

Seasonal cues of Arctic grayling movement in a small Arctic stream: the importance of surface water connectivity - Kurt C. Heim; Mark S. Wipfli; Matthew S. Whitman; Christopher D. Arp; Jeff Adams; Jeffrey A. Falke (Environmental Biology of Fishes, 2016)

Circulating T cell subsets are altered in individuals with chronic spinal cord injury - Rachel Monahan; Adam Stein; Katie Gibbs; Matthew Bank; Ona Bloom (Immunologic Research, 2015)

Rare niches and the ecological equivalence of species - Seth Haney; Matthew Cattivera; Adam M. Siepielski (Theoretical Ecology, 2015)

Determining the duration of Aphis glycines (Hemiptera: Aphididae) induced susceptibility effect in soybean - Adam J. Varenhorst; Michael T. McCarville; Matthew E. O’Neal (Arthropod-Plant Interactions, 2015)

Quantifying uncertainty and variable sensitivity within the US billion-dollar weather and climate disaster cost estimates - Adam B. Smith; Jessica L. Matthews (Natural Hazards, 2015)

Response - Matthew S. Ganio; J. D. Adams (European Journal of Applied Physiology, 2015)

Non-invasive estimation of hydration status changes through tear fluid osmolarity during exercise and post-exercise rehydration - Corey T. Ungaro; Adam J. Reimel; Ryan P. Nuccio; Kelly A. Barnes; Matthew D. Pahnke; Lindsay B. Baker (European Journal of Applied Physiology, 2015)

Effects of obesity on body temperature in otherwise-healthy females when controlling hydration and heat production during exercise in the heat - J. D. Adams; Matthew S. Ganio; Jenna M. Burchfield; Andy C. Matthews; Rachel N. Werner; Amanda J. Chokbengboun; Erin K. Dougherty; Alex A. LaChance (European Journal of Applied Physiology, 2015)

Estimating climate change effects on net primary production of rangelands in the United States - Matthew C. Reeves; Adam L. Moreno; Karen E. Bagne; Steven W. Running (Climatic Change, 2014)

Tropical forest fragmentation limits pollination of a keystone understory herb - Adam S. Hadley; Sarah J. K. Frey; W. Douglas Robinson; W. John Kress; Matthew G. Betts (Ecology, 2014)
Loss of native vegetation cover is thought to be a major driver of declines in pollination success worldwide. However, it is not well known whether reducing the fragmentation of remaining vegetation can ameliorate these negative effects. We tested the independent effects of composition vs. configuration on the reproductive success of a keystone tropical forest herb ( Heliconia tortuosa ). To do this we designed a large‐scale mensurative experiment that independently varied connected forest‐patch size (configuration) and surrounding amount of forest (composition). In each patch, we tested whether pollen tubes, fruit, and seed set were associated with these landscape variables. We also captured hummingbirds as an indication of pollinator availability in a subset of patches according to the same design. We found evidence for an effect of configuration on seed set of H. tortuosa , but not on other aspects of plant reproduction; proportion of seeds produced increased 40% across the gradient in patch size we observed (0.64 to >1300 ha), independent of the amount of forest in the surrounding landscape at both local and landscape scales. We also found that the availability of pollinators was dependent upon forest configuration; hummingbird capture rates increased three and one‐half times across the patch size gradient, independent of forest amount. Finally, pollinator availability was strongly positively correlated with seed set. We hypothesize that the effects of configuration on plant fitness that we observed are due to reduced pollen quality resulting from altered hummingbird availability and/or movement behavior. Our results suggest that prioritizing larger patches of tropical forest may be particularly important for conservation of this species.

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Naturally forced multidecadal variability of the Atlantic meridional overturning circulation - Matthew B. Menary; Adam A. Scaife (Climate Dynamics, 2014)

Pharmacokinetics and Metabolism of 2-Aminothiazoles with Antiprion Activity in Mice - B. Michael Silber; Satish Rao; Kimberly L. Fife; Alejandra Gallardo-Godoy; Adam R. Renslo; Deepak K. Dalvie; Kurt Giles; Yevgeniy Freyman; Manuel Elepano; Joel R. Gever; Zhe Li; Matthew P. Jacobson; et al. (Pharmaceutical Research, 2013)

Presphenoidal synchondrosis fusion in DBA/2J mice - Allysa Adams; Brandeis McBratney-Owen; Brittany Newby; Margot E. Bowen; Bjorn R. Olsen; Matthew L. Warman (Mammalian Genome, 2013)

Low temperature acclimation of photosynthetic capacity and leaf morphology in the context of phloem loading type - Matthew R. Dumlao; Anza Darehshouri; Christopher M. Cohu; Onno Muller; Jennifer Mathias; William W. Adams; Barbara Demmig-Adams (Photosynthesis Research, 2012)

The development of 20 microsatellite loci for the Australian marine mollusk, Donax deltoides, through next generation DNA sequencing - Adam D. Miller; Vincent L. Versace; Ty Matthews; Kate C. Bowie (Conservation Genetics Resources, 2012)

Conservation status of eulachon in the California Current - Richard G Gustafson; Michael J Ford; Peter B Adams; Jonathan S Drake; Robert L Emmett; Kurt L Fresh; Mindy Rowse; Elizabeth A K Spangler; Robert E Spangler; David J Teel; Matthew T Wilson (Fish and Fisheries, 2012)
Eulachon ( Thaleichthys pacificus ), an anadromous smelt in the Northeast Pacific Ocean was examined for listing under the USA’s Endangered Species Act (ESA). A southern Distinct Population Segment (DPS) of eulachon – that occurs in the California Current and is composed of numerous subpopulations that spawn in rivers from northern California to northern British Columbia – was identified on the basis of ecological and environmental characteristics, and to a lesser extent, genetic and life history variation. Although the northern terrestrial boundary of this DPS remains uncertain, our consensus opinion was that this northern boundary occurs south of the Nass River and that the DPS was discrete from more northern eulachon, as well as significant to the biological species as a whole and thus is a ‘species’ under the ESA. Eulachon have been nearly absent in northern California for over two decades, have declined in the Fraser River by over 97% in the past 10 years, and are at historically low levels in other British Columbia rivers in the DPS, and nearly so in the Columbia River. Major threats to southern eulachon include climate change impacts on ocean and freshwater habitat, by‐catch in offshore shrimp trawl fisheries, changes in downstream flow timing and intensity owing to dams and water diversions, and predation. These threats, together with large declines in abundance, indicate that the southern DPS of eulachon is at moderate risk of extinction throughout all of its range. The southern DPS was listed as threatened under the ESA in May 2010 – the first marine forage fish to be afforded these statutory protections, which apply only to waters under U.S. jurisdiction.

Lava Geochemistry as a Probe into Crustal Formation at the East Pacific Rise - Michael Perfit; V. Dorsey Wanless; W. Ian Ridley; Emily Klein; Matthew Smith; Adam Goss; Jillian Hinds; Scott Kutza; Daniel Fornari (Oceanography, 2012)

Human Dimensions - Bob Tjaden; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Timothy Gallaher; John Kushla; James Henderson; Andrew Londo; Melissa Kreye; Damian Adams; Tatiana Borisova; Francisco Escobedo; et al. (Journal of Forestry, 2011)
12The University of MD Extension (UME) has been very effective in teaching forest landowners concepts and principles of forest management through seminars, workshops and field days. After evaluating these techniques and recognizing people learn differently, new delivery methods were developed. UME developed a landowner based forestry correspondence course in two formats, first a traditional paper then a web based version. These were developed to support the range of ages, learning styles, high-speed internet availability and computer knowledge. Both versions lead the learner through the components of a forest stewardship plan. Upon course completion, the student has the framework of a forest stewardship plan in a format acceptable for State Forester approval. This has helped the State Forester meet forest stewardship plan goals during a significant decline of personnel who normally assist forest landowners. The courses have also helped forest landowners meet the NRCS requirements of having a plan in order to qualify for certain federal cost share programs. We are constantly adapting the courses based on course evaluations, new issues and programs, and innovative forest management techniques. Evaluations are performed upon the completion of the course to assist in measuring overall course effectiveness, student success, plan objectives and any enhancements necessary to improve the course. There is also a follow-up evaluation performed five years after completion to evaluate plan implementation, behavioral changes, knowledge maintained, acres impacted, financial impacts, and direct contacts of the students. Data from all evaluations will be presented in the poster as well as lesson learned.

Public Lands Management Issues - Patrick Davis; Robert Malmsheimer; Eddie Bevilacqua; Terry Haines; Craig Wilcox; Robert Lefevre; Dan Rees; Tom St. Clair; Eric Miller; Terry Craigg; Paul Adams; Douglas Osborne; et al. (Journal of Forestry, 2011)
389Humans are responsible for nearly seventy thousand wildfires in the US each year, and human-caused fires have burned more than 2 million acres in five of the past ten years. Wildfires are a major contributor to US greenhouse gas emissions, adding 126.4 million metric tons of carbon dioxide into the atmosphere each year. These emissions can be significantly reduced with improved wildfire management strategies. This research examines the connection between human-caused fire proximity to physical characteristics, criminal activities, and other factors within National Forests. It presents a spatial pattern model that predicts the likelihood of fire ignition location based on physical attributes, such as: the spatial location of fire ignition crimes and other crimes on national forests, and the spatial location of national forest physical characteristics (e.g., roads, trails, recreational/unique resources, etc.). This research will present natural resource managers with practical applications of spatial analysis techniques utilizing GIS, as well as help public land managers target and deploy personnel in areas most prone to human fire ignitions during times of high fire risk.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Near real-time Feed On Offer (FOO) from MODIS for early season grazing management of Mediterranean annual pastures - Richard C. G. Smith; Matthew Adams; Stewart Gittins; Steve Gherardi; Duncan Wood; Stefan Maier; Richard Stovold; Graham Donald; Sarfraz Khohkar; Adrian Allen (International Journal of Remote Sensing, 2011)

Ecological boundary detection using Bayesian areal wombling - Matthew C. Fitzpatrick; Evan L. Preisser; Adam Porter; Joseph Elkinton; Lance A. Waller; Bradley P. Carlin; Aaron M. Ellison (Ecology, 2010)
The study of ecological boundaries and their dynamics is of fundamental importance to much of ecology, biogeography, and evolution. Over the past two decades, boundary analysis (of which wombling is a subfield) has received considerable research attention, resulting in multiple approaches for the quantification of ecological boundaries. Nonetheless, few methods have been developed that can simultaneously (1) analyze spatially homogenized data sets (i.e., areal data in the form of polygons rather than point‐reference data); (2) account for spatial structure in these data and uncertainty associated with them; and (3) objectively assign probabilities to boundaries once detected. Here we describe the application of a Bayesian hierarchical framework for boundary detection developed in public health, which addresses these issues but which has seen limited application in ecology. As examples, we analyze simulated spread data and the historic pattern of spread of an invasive species, the hemlock woolly adelgid ( Adelges tsugae ), using county‐level summaries of the year of first reported infestation and several covariates potentially important to influencing the observed spread dynamics. Bayesian areal wombling is a promising approach for analyzing ecological boundaries and dynamics related to changes in the distributions of native and invasive species.

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Electrophysiological properties of isthmic neurons in frogs revealed by in vitro and in vivo studies - Matthew S. Caudill; Adam T. Eggebrecht; Edward R. Gruberg; Ralf Wessel (Journal of Comparative Physiology A, 2010)

The Albedo Effect and Forest Carbon Offset Design - Matthew Thompson; Darius Adams; K. Norman Johnson (Journal of Forestry, 2009)
Forestry and land-use change are often considered in the context of a greenhouse gas cap-and-trade program, in recognition of their influence on net carbon flux and their ability to mitigate climate change via increased carbon sequestration. The climatic impacts of forests are not limited to atmospheric greenhouse gas concentrations, however, and a growing body of research suggests that albedo-related climatic changes stemming from land-use change may diminish or counteract the climatic benefits of sequestration. Because forests are generally darker than bare or agricultural land they absorb relatively more solar radiation, which may exert a local warming influence. This phenomenon is known as the “albedo effect.” Thus, a “carbon-only” accounting approach that ignores albedo impacts can significantly overestimate the climatic benefit of offsets, in particular, afforestation. In the worst case this could result in a forest offset actually contributing to warming and, in general, may reduce the environmental effectiveness of some forest offsets. Therefore a cap-and-trade system design question is whether to recognize the albedo effect into forest offset accounting frameworks. We propose that forest offset design moves toward a “carbon-equivalent” accounting approach that aggregates the climatic impacts of sequestration and of surface albedo when evaluating forest offset projects. This change would result in climate mitigation efforts taking a more targeted geographic approach that emphasizes maintaining or increasing forest cover in the tropics, and that avoids afforestation in boreal and high-latitude temperate regions. Currently developing regional cap-and-trade systems in North America, however, give afforestation projects priority for offset consideration. By staying on the current path, efforts in these initiatives directed toward forest offsets may be inefficient or ineffective and, at worst, counterproductive, in large parts of the area they cover. Incorporating both carbon and albedo effects into policymaking will lead to more informed and effective forest offset design.

Further characterization of the discriminative stimulus properties of the atypical antipsychotic drug clozapine in C57BL/6 mice: role of 5-HT2A serotonergic and α1 adrenergic antagonism - Scott D. Philibin; D. Matthew Walentiny; Sarah A. Vunck; Adam J. Prus; Herbert Y. Meltzer; Joseph H. Porter (Psychopharmacology, 2009)

Modeling the Effects of Anthropogenic Habitat Change on Savanna Snake Invasions into African Rainforest - ADAM H. FREEDMAN; WOLFGANG BUERMANN; MATTHEW LEBRETON; LAURENT CHIRIO; THOMAS B. SMITH (Conservation Biology, 2009)
We used a species‐distribution modeling approach, ground‐based climate data sets, and newly available remote‐sensing data on vegetation from the MODIS and Quick Scatterometer sensors to investigate the combined effects of human‐caused habitat alterations and climate on potential invasions of rainforest by 3 savanna snake species in Cameroon, Central Africa: the night adder (Causus maculatus), olympic lined snake (Dromophis lineatus), and African house snake (Lamprophis fuliginosus). Models with contemporary climate variables and localities from native savanna habitats showed that the current climate in undisturbed rainforest was unsuitable for any of the snake species due to high precipitation. Limited availability of thermally suitable nest sites and mismatches between important life‐history events and prey availability are a likely explanation for the predicted exclusion from undisturbed rainforest. Models with only MODIS‐derived vegetation variables and savanna localities predicted invasion in disturbed areas within the rainforest zone, which suggests that human removal of forest cover creates suitable microhabitats that facilitate invasions into rainforest. Models with a combination of contemporary climate, MODIS‐ and Quick Scatterometer‐derived vegetation variables, and forest and savanna localities predicted extensive invasion into rainforest caused by rainforest loss. In contrast, a projection of the present‐day species‐climate envelope on future climate suggested a reduction in invasion potential within the rainforest zone as a consequence of predicted increases in precipitation. These results emphasize that the combined responses of deforestation and climate change will likely be complex in tropical rainforest systems.

Raman Chemical Imaging for Ingredient-specific Particle Size Characterization of Aqueous Suspension Nasal Spray Formulations: A Progress Report - William H. Doub; Wallace P. Adams; John A Spencer; Lucinda F. Buhse; Matthew P. Nelson; Patrick J. Treado (Pharmaceutical Research, 2007)

Site assessment of a woody crop where a shallow hardpan soil layer constrained plant growth - Gabriella Pracilio; Keith R. J. Smettem; Don Bennett; Richard J. Harper; Matthew L. Adams (Plant and Soil, 2006)

Does information of predators influence general wariness? - Jessica L. Adams; Kari W. Camelio; Matthew J. Orique; Daniel T. Blumstein (Behavioral Ecology and Sociobiology, 2006)

Evidence for adiabatic decompression melting in the Southern Mariana Arc from high-Mg lavas and melt inclusions - Edward J. Kohut; Robert J. Stern; Adam J. R. Kent; Roger L. Nielsen; Sherman H. Bloomer; Matthew Leybourne (Contributions to Mineralogy and Petrology, 2006)

Determination of Spatial Distribution Patterns of Clay and Plant Available Potassium Contents in Surface Soils at the Farm Scale using High Resolution Gamma Ray Spectrometry - Gabriella Pracilio; Matthew L. Adams; Keith R. J. Smettem; Richard J. Harper (Plant and Soil, 2006)

Why Are Young and Old Repetitive Elements Distributed Differently in the Human Genome? - Elise M.S. Belle; Matthew T. Webster; Adam Eyre-Walker (Journal of Molecular Evolution, 2005)

The impact of microsatellite electromorph size homoplasy on multilocus population structure estimates in a tropical tree ( Corythophora alta ) and an anadromous fish ( Morone saxatilis ) - RACHEL I. ADAMS; KYLE M. BROWN; MATTHEW B. HAMILTON (Molecular Ecology, 2004)
Microsatellite allelic states are determined by electrophoretic sizing of polymerase chain reaction fragments to define electromorphs. Numerous studies have documented that identical microsatellite electromorphs are potentially heterogeneous at the DNA sequence level, a phenomenon called electromorph size homoplasy. Few studies have examined the impact of electromorph size homoplasy on estimates of population genetic parameters. We investigated the frequency of microsatellite electromorph size homoplasy for 12 loci in the tropical tree Corythophora alta and 11 loci in the anadromous fish Morone saxatilis by sequencing 14–23 homozygotes per locus sampled from multiple populations for a total of 453 sequences. Sequencing revealed no homoplasy for M. saxatilis loci. Seven C. alta loci exhibited homoplasy, including single and compound repeat motifs both with and without interruptions. Between 12.5 and 42.9% of electromorphs sampled per locus showed size homoplasy. Two methods of correction for homoplasy in C. alta generally produced little or no change in single‐locus estimates of R ST , except for two loci in which some additional differentiation among populations was revealed. Twelve‐locus estimates of R ST (including the seven loci corrected for homoplasy) were slightly greater than estimates from uncorrected data, although the 95% confidence intervals overlapped. The frequency of methodological errors such as clerical mistakes or sample mislabelling per genotype scored was estimated at 5.4 and 7.3% for C. alta and M. saxatilis , respectively. Simulations showed that the increase in R ST produced by homoplasy correction was only slightly larger than variation in R ST estimates expected to be caused by methodological errors.

Genes controlling seed dormancy and pre-harvest sprouting in a rice-wheat-barley comparison - Chengdao Li; Peixiang Ni; Michael Francki; Adam Hunter; Yong Zhang; David Schibeci; Heng Li; Allen Tarr; Jun Wang; Mehmet Cakir; Jun Yu; Matthew Bellgard; et al. (Functional & Integrative Genomics, 2004)

Comparative organization of wheat homoeologous group 3S and 7L using wheat-rice synteny and identification of potential markers for genes controlling xanthophyll content in wheat - Meredith Carter; Karon Ryan; Adam Hunter; Matthew Bellgard; Rudi Appels; Michael Francki (Functional & Integrative Genomics, 2004)

Leaf respiration is differentially affected by leaf vs. stand‐level night‐time warming - Kevin L. Griffin; Matthew Turnbull; Ramesh Murthy; Guanghui Lin; John Adams; Blake Farnsworth; Tilak Mahato; Guerric Bazin; Mark Potasnak; Joe A. Berry (Global Change Biology, 2002)
Plant respiration is an important physiological process in the global carbon cycle serving as a major carbon flux from the biosphere to the atmosphere. Respiration is sensitive to temperature providing a link between environmental variability, climate change and the global carbon cycle. We measured leaf respiration in Populus deltoides after manipulating the air temperature surrounding part of a single leaf, and compared this to the temperature response of the same leaves after manipulating the temperature of the stand. The short‐term temperature response of respiration (Q 10 – change in the respiration rate with a 10 °C increase in leaf temperature) was 1.7 when the leaf temperature was manipulated, but 2.1 when the stand‐level temperature was changed. As a result, total night‐time carbon release during the five‐day experiment was 21% lower when using the Q 10 estimates from the tradition leaf manipulation compared to the stand‐level manipulation. We conclude that the temperature response of leaf respiration is related to whole plant carbon and energy demands, and that appropriate experimental procedures are required in examining respiratory CO 2 release under variable temperature conditions.

Generation and exploration of a dense genetic map in a region of a QTL affecting corpora lutea in a Meishan × Yorkshire cross - Martin H. Braunschweig; Adam A. Paszek; Joel I. Weller; Yang Da; Rachel J. Hawken; Matthew B. Wheeler; Lawrence B. Schook; Leeson J. Alexander (Mammalian Genome, 2001)

A 2500 year sediment record from Fayetteville Green Lake, New York: evidence for anthropogenic impacts and historic isotope shift - Martin F. Hilfinger IV; Henry T. Mullins; Adam Burnett; Matthew E. Kirby (Journal of Paleolimnology, 2001)

Managing Uncertainty in Site-Specific Management: What is the Best Model? - Matthew L. Adams; Simon Cook; Robert Corner (Precision Agriculture, 2000)

Measurement of Void Size Correlation in Inhomogeneous Porous Media - Toby Mathews; G. Peter. Matthews; Cathy J. Ridgway; Adam. K. Moss (Transport in Porous Media, 1997)

Genetic diversity at an oncogene locus and in mitochondrial DNA between populations of cancer-prone atlantic tomcod - Isaac I. Wirgin; Matthew D'Amore; Cheryl Grunwald; Adam Goldman; Seymour J. Garte (Biochemical Genetics, 1990)

Estimating medullary chemoreceptor blood flow from ventilatory-CO2 response transients: Theory and data from anesthetized dogs - J. Milton Adams; William P. Glasheen; Matthew L. Severns (Annals of Biomedical Engineering, 1984)